Laminate and display device
The laminate, comprising a first phaser, a vertically polarized film, a polarizer, and a second phaser, addresses the issue of white spots in organic EL display devices when viewed through polarized sunglasses, achieving improved visibility and reduced internal reflection.
Patent Information
- Application Number
- JP2024143404
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-09
AI Technical Summary
Existing organic EL display devices with laminates suffer from white spots when viewed from an angle through polarized sunglasses.
A laminate comprising a first phaser with in-plane phase difference, a vertical polarizing film made from a cured product of a polymerizable liquid crystal compound and a dichroic dye, a polarizer, and a second phaser, optimized with specific absorption maximum wavelengths and phase difference values to suppress white spots.
The laminate effectively suppresses white spots in organic EL display devices when viewed from an angle through polarized sunglasses, enhancing visibility and reducing internal reflection.
Smart Images

Figure 2025058922000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a display device. [Background technology]
[0002] Image display devices such as organic electroluminescence (EL) display devices are widely used in mobile phones, smartphones, notebook computers, information terminals, etc. Attempts have been made to improve the functionality of such image display devices according to their applications and the circumstances in which they are used.
[0003] For example, Patent Document 1 discloses a laminate in which a light absorbing anisotropic film (vertical polarizing film), a horizontally aligned retardation film i (first retarder), a polarizer, and a horizontally aligned retardation film ii (second retarder) are laminated in this order. An organic EL display device to which this laminate is applied can suppress internal reflection of the organic EL display device when viewed from the front, thereby providing excellent visibility of the screen, by adjusting the in-plane retardation and slow axis direction of the horizontally aligned retardation film ii (second retarder). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-176121 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, it has been found that when an image display device including the laminate described in Patent Document 1 is viewed obliquely through polarized sunglasses during white display, spots are generated.
[0006] Therefore, an object of the present invention is to provide a laminate capable of realizing an organic EL display device in which white display spots are suppressed when viewed obliquely through polarized sunglasses. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention includes the following preferred embodiments.
[0008] [1] A laminate including, in this order, a first retarder, a vertical polarizing film, a polarizer, and a second retarder, the first retarder is a retarder exhibiting an in-plane retardation, an angle between a slow axis of the first retarder and an absorption axis of the polarizer is 35° or more and 55° or less, or 125° or more and 145° or less; The vertical polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye, and is represented by the following formulas (1) and (2): 0.001≦AxC≦0.3 (1) AxC(z=60) / AxC>2 (2) [In the formulas (1) and (2), AxC and AxC(z=60) are absorbances at the absorption maximum wavelength of the vertical polarizing film in the wavelength range of 400 to 750 nm, AxC represents the absorbance of linearly polarized light oscillating in the x-axis direction, and AxC(z=60) represents the absorbance of linearly polarized light oscillating in the x-axis direction when the vertical polarizing film is rotated 60° around the y-axis as the rotation axis, Here, the x-axis is an arbitrary direction in the plane of the vertical polarizing film, the y-axis is a direction perpendicular to the x-axis in the film plane, and the z-axis is the thickness direction of the vertical polarizing film. Meet the laminate. [2] The vertical polarizing film has an absorption maximum wavelength in an oblique direction of 500 nm or more and less than 700 nm, and the first phase shifter has the following formula (3): Re(450)≦135nm (3) [In formula (3), Re(450) represents the in-plane retardation value of the first retarder at a wavelength of 450 nm] The laminate according to [1], which satisfies the above. [3] The vertical polarizing film has an absorption maximum wavelength in an oblique direction of 400 nm or more and less than 500 nm, and the first phase shifter has the following formulas (4) and (5): Re(550)≧95nm (4) Re(650)≧95nm (5) [In formulas (4) and (5), Re(λ) represents the in-plane retardation value of the first retarder at a wavelength of λ nm] The laminate according to [1], which satisfies at least one of the above. [4] The vertical polarizing film has an absorption maximum wavelength in an oblique direction of 400 nm or more and less than 600 nm, and the first phase shifter has the following formula (6): Re(650)≧95nm (6) [In formula (6), Re(650) represents the in-plane retardation value of the first retarder at a wavelength of 650 nm] The laminate according to [1], which satisfies the above. [5] The vertical polarizing film has a maximum absorption wavelength in an oblique direction of 600 to 700 nm, and the first retarder has formulas (7) and (8) below: Re(450)≦135nm (7) Re(550)≦150nm (8) [In formulas (7) and (8), Re(λ) represents the in-plane retardation value of the first retarder at a wavelength of λ nm] The laminate according to [1], which satisfies at least one of the above. [6] The laminate according to any one of [1] to [5], wherein the second retarder includes a cured film of a composition containing a polymerizable liquid crystal compound. [7] The laminate according to any one of [1] to [5], wherein the polarizer includes a cured film of a composition containing a polymerizable liquid crystal compound and a dichroic dye. [8] An organic electroluminescence display device comprising the laminate according to any one of [1] to [7]. Effect of the Invention
[0009] According to the present invention, it is possible to provide a laminate capable of realizing an organic EL display device in which white display spots are suppressed when viewed obliquely through polarized sunglasses. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a layer structure of a laminate of the present invention. [Diagram 2]FIG. 1 is a schematic cross-sectional view showing an example of a layer structure of a laminate of the present invention. [Diagram 3] FIG. 2 is a diagram showing the X-axis, Y-axis, and Z-axis in a vertical polarizing film contained in a laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0012] The laminate of the present invention includes, in this order, a first retarder exhibiting in-plane retardation, a vertical polarizing film that is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye, a polarizer, and a second retarder. Hereinafter, an example of the layer structure of the laminate of the present invention will be described with reference to Figs. 1 and 2, but the laminate of the present invention is not limited to these embodiments.
[0013] 1 includes, in this order, a first retarder 1, a vertical polarizing film 2, a polarizer 3, and a second retarder 4. The laminate of the present invention is usually incorporated into an image display device or the like so that the first retarder is located on the viewing side. As shown in FIG. 2, the second phase shifter 4 may be incorporated as one of the phase shifters constituting a multiple phase shift plate 11. In this case, the multiple phase shift plate 11 includes an additional phase shifter 5 different from the second phase shifter 4. The laminate of the present invention may further include other layers in addition to the first phase shifter, the vertical polarizing film, the polarizer, and the second phase shifter, as long as the effects of the present invention are not affected. Examples of the other layers include protective layers such as a hard coat layer and a transparent protective film, a substrate layer, and a pressure-sensitive adhesive layer. These other layers are usually non-oriented and optically isotropic layers, and are colorless and transparent.
[0014] The vertical polarizing film is a cured product in which a polymerizable liquid crystal compound and a dichroic dye are cured in a state in which they are oriented in a direction perpendicular to the plane of the obtained cured product, and is represented by the following formulas (1) and (2): 0.001≦AxC≦0.3 (1) AxC(z=60) / AxC>2 (2) [In the formulas (1) and (2), AxC and AxC(z=60) are absorbances at the absorption maximum wavelength of the vertical polarizing film in the wavelength range of 400 to 750 nm, AxC represents the absorbance of linearly polarized light oscillating in the x-axis direction, and AxC(z=60) represents the absorbance of linearly polarized light oscillating in the x-axis direction when the vertical polarizing film is rotated 60° around the y-axis as the rotation axis, where the x-axis is an arbitrary direction in the plane of the vertical polarizing film, the y-axis is a direction perpendicular to the x-axis in the film plane, and the z-axis is the thickness direction of the vertical polarizing film. The above formula (1) means that the absorbance in the front direction of the vertical polarizing film is 0.001 or more and 0.3 or less, and it can be said that the smaller the value of AxC, the more precisely the dichroic dye is oriented in the vertical direction relative to the plane of the obtained vertical polarizing film. In addition, as shown in formula (2), AxC (z = 60) is sufficiently large compared to AxC, so that when light is incident on the vertical polarizing film from an oblique direction on the polarizer side, the wavelength component that gives the maximum absorbance AxC (z = 60) in the oblique direction of the vertical polarizing film is absorbed, and the remaining wavelength component is transmitted. This transmitted wavelength component is incident on the first phase shifter from an oblique direction and is emitted from the first phase shifter in an oblique direction. Although the details are unclear, it is thought that one of the reasons why the light incident on the oblique direction and transmitted passes through the first phase shifter that shows a phase difference in the plane can suppress display spots when a white display is viewed obliquely through sunglasses. When the first phase shifter functions as a λ / 4 plate for the wavelength components incident and transmitted in the oblique direction, the light exiting obliquely is perceived as being closer to circularly polarized light, which is preferable because it is believed that this can more effectively suppress display spots when a white display is viewed obliquely through sunglasses. In this specification, all absorbances are those measured without the influence of interface reflection during measurement. Examples of a method for removing the influence of interface reflection include a method in which, using a spectrophotometer, the absorbance at a long wavelength such as 800 nm where the absorption of the compound is negligible is set to 0, and the absorbance at a wavelength in the range where the absorption of the compound exists is measured under this condition.
[0015] If the value of AxC exceeds 0.3, the screen becomes dark (luminance is reduced), so the value of AxC is preferably 0.1 or less, more preferably 0.05 or less. The lower limit of the value of AxC is usually 0.001 or more, preferably 0.003 or more, and more preferably 0.005 or more.
[0016] The above AxC(z=60) can be measured by rotating the vertical polarizing film by 60° around the y-axis as the axis of rotation, and then applying the same linearly polarized light as that used to measure Ax. Here, the film is rotated by 60° around the y-axis as the axis of rotation, in the direction of incidence of the linearly polarized light, with the film in the state where Ax was measured. If the value of AxC(z=60) / AxC is 2 or less, it is difficult to obtain good optical anisotropy, and visibility is deteriorated when viewing the organic EL device obliquely through polarized sunglasses during white display. Therefore, the value of AxC(z=60) / AxC is preferably 3 or more, more preferably 5 or more. On the other hand, if the value of AxC(z=60) / AxC is too large, it is difficult to obtain or manufacture the organic EL device, so the value of AxC(z=60) / AxC is preferably 50 or less, more preferably 30 or less, even more preferably 20 or less, and particularly preferably 15 or less. In addition, AxC(z=60) is preferably 0.01 or more, more preferably 0.03 or more, even more preferably 0.04 or more, and is preferably 1.0 or less, more preferably 0.5 or less, even more preferably 0.3 or less, and particularly preferably 0.2 or less. The absorbance of linearly polarized light vibrating in the y-axis direction is represented as AyC, but in the vertical polarizing film described in the present invention, AxC and AyC are usually almost equal. If AxC and AyC are different, the film will have in-plane dichroism, and in this case, the vertical polarizing film will tend to be colored more strongly in the front hue.
[0017] In the present invention, AxC and AxC(Z=60) in the vertical polarizing film can be controlled by, for example, adjusting the film thickness, the conditions of the manufacturing process, the types and amounts of the polymerizable liquid crystal compound and the dichroic dye that constitute the vertical polarizing film, etc. In addition, the value of AxC(z=60) / AxC is generally about 2 to 10 when the polymerizable liquid crystal compound is a nematic liquid crystal, and about 5 to 30 when the polymerizable liquid crystal compound is a smectic liquid crystal, and can be appropriately selected according to the desired optical properties.
[0018] In the present invention, the vertical polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye. The polymerizable liquid crystal compound means a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group. The polymerizable liquid crystal compound is not particularly limited as long as it can form a vertical polarizing film that satisfies the above formulas (1) and (2), and for example, a polymerizable liquid crystal compound conventionally known in the field of retardation films can be used.
[0019] The polymerizable group refers to a group that can participate in a polymerization reaction. The photopolymerizable group refers to a polymerizable group that can participate in a polymerization reaction by a reactive species generated from a photopolymerization initiator, such as an active radical or an acid. Examples of the photopolymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property exhibited by the polymerizable liquid crystal compound may be a thermotropic liquid crystal or a lyotropic liquid crystal, but a thermotropic liquid crystal is preferred in terms of the ability to precisely control the film thickness. In addition, the phase order structure in the thermotropic liquid crystal may be a nematic liquid crystal or a smectic liquid crystal. From the viewpoint of a small AxC value and a large AxC(z=60) / AxC value, a smectic liquid crystal is preferred. The polymerizable liquid crystal compounds can be used alone or in combination of two or more kinds.
[0020] The dichroic dye in the present invention refers to a dye having a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction. The dichroic dye is not particularly limited as long as it has such a property and can form a vertical polarizing film that satisfies the above formulas (1) and (2). The dichroic dye may be a dye or a pigment, and may be a combination of two or more dyes, a combination of two or more pigments, or a combination of a dye and a pigment.
[0021] In the present invention, the first phase shifter is a phase shifter exhibiting a phase difference in the plane, and specifically may be, for example, a phase shifter film formed by stretching a thermoplastic resin film and exhibiting a phase difference in the plane, or a phase shifter film composed of a polymer of a polymerizable liquid crystal compound and exhibiting a phase difference in the plane. In the present disclosure, the phase shifter film as the first phase shifter is composed of a layer composed of a polymer of a polymerizable liquid crystal compound alone, or has a two-layer structure consisting of this layer and an alignment layer. It is preferable that the in-plane phase difference Re(λ) of the first phase shifter exhibits an in-plane phase difference equivalent to approximately 1 / 4 of the wavelength λ in the visible light wavelength range. Such a first phase shifter can function as a so-called λ / 4 plate.
[0022] In the present invention, the angle between the slow axis of the first phase shifter and the absorption axis of the polarizer described later is usually 35° to 55° or 125° to 145°, preferably 40° to 50° or 130° to 140°, and ideally 45° or 135°. When the first phase shifter is a λ / 4 plate exhibiting the above-mentioned in-plane retardation and the angle between its slow axis and the absorption axis of the polarizer described later is within the above-mentioned range, the light emitted from the image display device through the polarizer, the vertical polarizing film, and the first phase shifter toward the front can be circularly polarized. Therefore, the displayed image can be easily viewed even from the front through sunglasses. The angle between the slow axis of the first phase shifter and the absorption axis of the polarizer described later can be adjusted within the above-mentioned range, for example, by adjusting the bonding angle, manufacturing the first phase shifter so that the slow axis or the absorption axis of the polarizer is set to a predetermined angle in advance, and bonding them together by roll to roll.
[0023] In a preferred embodiment of the present invention, the first phase shifter preferably functions as a λ / 4 plate for the wavelength component transmitted through the vertical polarizing film. Specifically, for example, when the maximum absorption wavelength of the vertical polarizing film in the oblique direction is 500 nm to 700 nm, light with a wavelength of less than 500 nm, for example, 450 nm, is relatively easily transmitted, so that the first phase shifter satisfies the following formula (3): Re(450)≦135nm (3) [In formula (3), Re(450) represents the in-plane retardation value of the first retarder at a wavelength of 450 nm] It is preferable that the following is satisfied. Re(450) of the first retarder is more preferably 125 nm or less, further preferably 125 nm or less, further more preferably 120 nm or less, and particularly preferably 110 nm or less. Moreover, Re(450) is usually 85 nm or more, preferably 90 nm or more, and more preferably 95 nm or more.
[0024] In the present invention, the maximum absorption wavelength of the vertical polarizing film in an oblique direction can be adjusted to a desired range, for example, by appropriately adjusting the types of dichroic dyes contained in the vertical polarizing film, their combinations, ratios, etc. In addition, the maximum absorption wavelength of the vertical polarizing film in an oblique direction can be measured, for example, by a spectrophotometer. In detail, it can be measured, for example, according to the method described in the Examples below.
[0025] The in-plane retardation value Re(λ) of the first retarder is expressed by the formula: Re(λ)=(nx(λ)-ny(λ))×d [In the formula, nx(λ) represents the principal refractive index at a wavelength of λ nm in the plane of the first retarder, ny(λ) represents the refractive index at a wavelength of λ nm in the same plane as nx and in a direction perpendicular to the direction of nx, and d represents the film thickness of the first retarder] It can be calculated from. Therefore, in order to obtain a desired in-plane retardation value, it is sufficient to adjust the three-dimensional refractive index and the film thickness d, and specifically, for example, the thickness of the first retarder; the type and / or amount of additive contained in the first retarder; the manufacturing conditions of the first retarder, etc., can be appropriately adjusted to adjust it to a desired range. In addition, the in-plane retardation value can be measured, for example, using a retardation measuring device.
[0026] In a preferred embodiment of the laminate of the present invention, for example, when the absorption maximum wavelength in an oblique direction of the vertical polarizing film is 400 nm or more and less than 500 nm, light with a wavelength of more than 500 nm is relatively easily transmitted, so that the first phase shifter is represented by the following formulas (4) and (5): Re(550)≧95nm (4) Re(650)≧95nm (5) [In formulas (4) and (5), Re(λ) represents the in-plane retardation value of the first retarder at a wavelength of λ nm] It is preferable that at least one of the above conditions, and more preferably both of them, is satisfied. The Re(550) of the first retarder is preferably 120 nm or more, more preferably 130 nm or more, even more preferably 135 nm or more, and particularly preferably 140 nm or more. The Re(650) is preferably 120 nm or more, more preferably 130 nm or more, and even more preferably 135 nm or more. The Re(550) is usually 180 nm or less, preferably 165 nm or less, and even more preferably 150 nm or less, and the Re(650) is usually 200 nm or less, preferably 180 nm or less, and even more preferably 160 nm or less. From the viewpoint of suppressing coloration of internally reflected light during black display, it is more preferable that the first retarder satisfies both of the above formulas (4) and (5).
[0027] In another preferred embodiment of the laminate of the present invention, for example, when the absorption maximum wavelength in an oblique direction of the vertical polarizing film is 400 nm or more and less than 600 nm, light with a wavelength of more than 600 nm is relatively easily transmitted, so that the first phase shifter is represented by the following formula (6): Re(650)≧95nm (6) [In formula (6), Re(650) represents the in-plane retardation value of the first retarder at a wavelength of 650 nm] It is preferable that the following is satisfied. Re(650) is preferably 110 nm or more, more preferably 120 nm or more, even more preferably 130 nm or more, and particularly preferably 140 nm or more. Re(650) is usually 200 nm or less, preferably 180 nm or less, and even more preferably 160 nm or less.
[0028] In a preferred embodiment of the laminate of the present invention, for example, when the vertical polarizing film has an absorption maximum wavelength in an oblique direction of 600 to 700 nm, light having a wavelength of less than 600 nm is relatively easily transmitted, and therefore the first phase shifter is represented by the following formulas (7) and (8): Re(450)≦135nm (7) Re(550)≦150nm (8) [In formulas (7) and (8), Re(λ) represents the in-plane retardation value of the first retarder at a wavelength of λ nm] It is preferable to satisfy at least one of the above, and preferably both. Re(450) is preferably 130 nm or less, more preferably 125 nm or less, even more preferably 115 nm or less, and particularly preferably 115 nm or less. Re(550) is preferably 140 nm or less, more preferably 130 nm or less, even more preferably 120 nm or less, and even more preferably 110 nm or less. Re(450) is usually 80 nm or more, preferably 85 nm or more, and even more preferably 90 nm or more, and Re(550) is usually 80 nm or more, preferably 90 nm or more, and even more preferably 95 nm or more.
[0029] In a preferred embodiment of the laminate of the present invention, the second retarder or the multiple retardation plate may be a so-called λ / 4 plate, and the in-plane retardation measured from the front may be approximately one-quarter of the wavelength λ (approximately λ / 4) in the visible light range. In a preferred embodiment, the second retarder or the multiple retardation plate may have a slow axis that is usually at approximately 45° to the absorption axis of the polarizer. When the second phase shifter or the multiple phase retardation plate is a so-called λ / 4 plate, the polarizer constituting the laminate of the present invention and the second phase shifter or the multiple phase retardation plate can function as a circular polarizing plate for light incident from the front of the polarizer side. On the other hand, the retardation value of the second phase shifter for light incident from an oblique direction on the polarizer side will be shifted from the actual in-plane retardation value of the second phase shifter. Similarly, the angle that the slow axis of the second phase shifter makes with the absorption axis of the polarizer will be shifted from 45°.
[0030] Therefore, the polarizer and the second retarder or the multiple retardation plate can function as an elliptical polarizer, not as a circular polarizer, for light incident from an oblique direction. In that case, when the organic EL display device is viewed from an oblique direction during black display, a small amount of light reflected inside the display device may appear colored. In the laminate of the present invention, since a vertical polarizing film containing a dye capable of absorbing light reflected inside the display device is located between the polarizer and the first retarder, in addition to suppressing spots visible when the organic EL display device is viewed from an oblique direction through polarized sunglasses during white display, coloring during black display can also be suppressed.
[0031] Each layer constituting the laminate of the present invention will be described in detail below.
[0032] <Vertical polarizing film> In the present invention, the vertical polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye.
[0033] The polymerizable liquid crystal compound forming the vertical polarizing film in the present invention may be either a nematic liquid crystal or a smectic liquid crystal, with the smectic liquid crystal being preferred from the viewpoint of absorption selectivity. When a polymerizable liquid crystal compound exhibiting smectic liquid crystallinity is used as the polymerizable liquid crystal compound forming the vertical polarizing film in the present invention, it is more preferable that the polymerizable liquid crystal compound is in a high-order smectic phase (high-order smectic liquid crystal state) from the viewpoint of realizing a higher degree of orientation order. Here, the high-order smectic phase means a smectic B phase, a smectic D phase, a smectic E phase, a smectic F phase, a smectic G phase, a smectic H phase, a smectic I phase, a smectic J phase, a smectic K phase, and a smectic L phase, and among these, a smectic B phase, a smectic F phase, and a smectic I phase are more preferable. The liquid crystallinity may be a thermotropic liquid crystal or a lyotropic liquid crystal, but a thermotropic liquid crystal is preferable in terms of enabling precise film thickness control. In addition, the polymerizable liquid crystal compound exhibiting smectic liquid crystallinity may be a monomer, but may also be an oligomer or a polymer in which a polymerizable group is polymerized.
[0034] The polymerizable liquid crystal compound exhibiting smectic liquid crystallinity is a liquid crystal compound having at least one polymerizable group, and from the viewpoint of improving the heat resistance of the vertical polarizing film, it is preferable that the liquid crystal compound has two or more polymerizable groups. Examples of the polymerizable group include a (meth)acryloyloxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an oxiranyl group, and an oxetanyl group. Among them, it is preferable that the polymerizable group contains a (meth)acryloyloxy group, because it is easy to manufacture, the heat resistance of the vertical polarizing film is easily improved, and the adhesion between the vertical polarizing film and the substrate is easily adjusted.
[0035] An example of the polymerizable liquid crystal compound exhibiting smectic liquid crystal properties is a compound represented by the following formula (Z) (hereinafter, sometimes referred to as "polymerizable liquid crystal compound (Z)"). [ka] [In formula (Z), X 1z and X 2zrepresent, independently of each other, a divalent aromatic group or a divalent alicyclic hydrocarbon group, in which a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. 1z and X 2z At least one of these is a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent. Y 1z is a single bond or a divalent linking group. nz is 1 to 3. If nz is 2 or more, multiple X 1z may be the same or different. X 2z is multiple X 1z In addition, when nz is 2 or more, a plurality of Y 1z may be the same as or different from each other. From the viewpoint of liquid crystallinity, nz is preferably 2 or more. U 1z represents a hydrogen atom or a (meth)acryloyloxy group. U 2z represents a polymerizable group. W 1z and W 2z are each independently a single bond or a divalent linking group. V 1z and V 2z each independently represents an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, and -CH 2 - may be replaced by -O-, -CO-, -S- or -NH-.
[0036] In the polymerizable liquid crystal compound (Z), X 1z and X 2zare each independently preferably an optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group, and X 1z and X 2z At least one of the groups is a 1,4-phenylene group which may have a substituent, or a cyclohexane-1,4-diyl group which may have a substituent, and is preferably a trans-cyclohexane-1,4-diyl group. Examples of the optional substituent of the 1,4-phenylene group which may have a substituent, or the cyclohexane-1,4-diyl group which may have a substituent include an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, and a butyl group, a cyano group, and a halogen atom such as a chlorine atom or a fluorine atom. It is preferably unsubstituted.
[0037] The polymerizable liquid crystal compound (Z) is represented by the formula (Z1): -(X 1 -Y 1 -) n -X 2 - (Z1) [where, X 1z , Y 1z , X 2z and nz have the same meanings as above] [hereinafter, referred to as partial structure (Z1)] is preferably an asymmetric structure, since this facilitates the development of smectic liquid crystal properties. The polymerizable liquid crystal compound (Z) in which the partial structure (Z1) is an asymmetric structure is, for example, a compound in which nz is 1 and one X 1z and X 2z In addition, the polymerizable liquid crystal compound (Z) may be a compound in which nz is 2 and two Y 1z A compound in which two Xs are the same structure. 1z are identical in structure to each other, and one X 2z These two X 1z A polymerizable liquid crystal compound (Z) with a structure different from that of the two X 1z Of the W 1z X binds to 1z But the other X 1z and X 2zThe structure is different from that of the other X 1z and X 2z Also included are polymerizable liquid crystal compounds (Z) having the same structure as each other. 1z are the same structure as each other, and three X 1z and one X 2z The polymerizable liquid crystal compound (Z) has a structure in which any one of the above is different from all of the other three.
[0038] Y 1z is -CH 2 CH 2 -, -CH 2 O-, -CH 2 CH 2 O-, -COO-, -OCOO-, single bond, -N=N-, -CR az =CR bz -, -C≡C-, -CR az =N- or -CO-NR az - is preferred. az and R bz each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1z is -CH 2 CH 2 More preferably, Y is -, -COO-, or a single bond. 1z If present, X 2z Y that binds to 1z is -CH 2 CH 2 -or-CH 2 O- is more preferred. 1z and X 2z When all of Y are the same structure, two or more Y 1z It is preferable that there is a plurality of Y 1z When the compound has a structure of asymmetric structure, the compound tends to exhibit smectic liquid crystallinity.
[0039] U 2z is the polymerizable group described above. 1zis a hydrogen atom or a polymerizable group. The polymerizable group is preferably a (meth)acryloyloxy group because it is easy to produce, the heat resistance of the vertical polarizing film is easily improved, and the adhesion between the vertical polarizing film and the base material is easily adjusted. The polymerizable group may be in a polymerized state or an unpolymerized state, but is preferably in an unpolymerized state.
[0040] V 1z and V 2z Examples of the alkanediyl group represented by the formula (I) include a methylene group, an ethylene group, a propane-1,3-diyl group, a butane-1,3-diyl group, a butane-1,4-diyl group, a pentane-1,5-diyl group, a hexane-1,6-diyl group, a heptane-1,7-diyl group, an octane-1,8-diyl group, a decane-1,10-diyl group, a tetradecane-1,14-diyl group, and an icosane-1,20-diyl group. 1z and V 2z is preferably an alkanediyl group having 2 to 12 carbon atoms, and more preferably an alkanediyl group having 6 to 12 carbon atoms.
[0041] Examples of the substituent that the alkanediyl group may have include a cyano group and a halogen atom. The alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted linear alkanediyl group.
[0042] W 1z and W 2z are each independently preferably a single bond, -O-, -S-, -COO- or -OCOO-, more preferably a single bond or -O-.
[0043] The polymerizable liquid crystal compound (Z) preferably has an asymmetric molecular structure in its molecular structure, and more specifically, is more preferably a polymerizable liquid crystal compound having the following partial structures (Aa) to (Ai). From the viewpoint of easily exhibiting high-order smectic liquid crystallinity, it is more preferably a polymerizable liquid crystal compound having the partial structure (Aa), (Ab) or (Ac). In the following (Aa) to (Ai), * represents a bond (single bond).
[0044] [ka]
[0045] Specific examples of the polymerizable liquid crystal compound (Z) include compounds represented by formulae (A-1) to (A-25). When the polymerizable liquid crystal compound (Z) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably a trans isomer.
[0046] [ka]
[0047] [ka]
[0048] [ka]
[0049] Among these, at least one selected from the group consisting of compounds represented by formula (A-2), formula (A-3), formula (A-4), formula (A-5), formula (A-6), formula (A-7), formula (A-8), formula (A-13), formula (A-14), formula (A-15), formula (A-16) and formula (A-17) is preferred. As the polymerizable liquid crystal compound (Z), one type may be used alone, or two or more types may be used in combination.
[0050] The polymerizable liquid crystal compound (Z) can be produced by a known method, for example, as described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4,719,156.
[0051] The polymerizable liquid crystal compound forming the vertical polarizing film is preferably a polymerizable liquid crystal compound having a maximum absorption wavelength between 300 and 400 nm. When the polymerizable liquid crystal composition contains a photopolymerization initiator, the polymerization reaction and gelation of the polymerizable liquid crystal compound may proceed during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound is 300 to 400 nm, even if the composition is exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species can be effectively suppressed. Therefore, it is advantageous in terms of long-term stability of the composition containing the polymerizable liquid crystal compound, and the alignment property and uniformity of the film thickness of the obtained liquid crystal cured film can be improved. The maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using a UV-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and examples thereof include chloroform.
[0052] From the viewpoint of increasing the alignment of the liquid crystal compound, the content of the liquid crystal compound in the liquid crystal composition forming the vertical polarizing film is preferably 70 parts by mass or more, more preferably 80 parts by mass or more, and preferably 99.5 parts by mass or less, more preferably 99 parts by mass or less, even more preferably 94 parts by mass or less, and even more preferably 92 parts by mass or less, relative to 100 parts by mass of the vertical polarizing film. The content of the liquid crystal compound can be calculated as the ratio of the liquid crystal compound to 100 parts by mass of the solid content of the liquid crystal composition forming the vertical polarizing film.
[0053] <Horizontal polarizing film> In the present invention, the horizontal polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye, and refers to a film in which the polymerizable liquid crystal film is horizontally aligned in a fixed direction within the film plane.
[0054] <Dichroic dye> The dichroic dye preferably has a maximum absorption wavelength (λMAX) in the range of 300 to 750 nm in the vertical polarizing film and the horizontal polarizing film. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, and anthraquinone dyes, among which azo dyes are preferred. Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, and stilbene azo dyes, and monoazo and bisazo dyes are preferred. The dichroic dyes may be used alone or in combination, but when polarization characteristics are required over the entire visible light range, it is preferred to combine two or more dichroic dyes. For example, a dichroic dye having an absorption maximum wavelength of 400 nm or more and less than 500 nm may be combined with a dichroic dye having an absorption maximum wavelength of 500 nm or more and less than 600 nm, or a dichroic dye having an absorption maximum wavelength of 500 nm or more and less than 600 nm may be combined with a dichroic dye having an absorption maximum wavelength of 600 nm or more and less than 700 nm. The absorbance of the dichroic dye can be measured by a spectrophotometer in a state where the dichroic dye is dissolved in a solvent such as chloroform that dissolves the dichroic dye.
[0055] The dichroic dyes constituting the vertical polarizing film and the horizontal polarizing film may be used alone or in combination of two or more. The type and / or content of the dichroic dye may be appropriately selected so as to produce a complementary color that cancels the coloring of the internally reflected light that is slightly obliquely emitted from the first retarder side during black display.
[0056] Examples of the azo dye include those represented by the formula (I): A 1 (-N=NA 2 ) p -N=NA 3 (I) [In formula (I), A 1 and A 3 A each independently represents a phenyl group which may have a substituent, a naphthyl group which may have a substituent, or a monovalent heterocyclic group which may have a substituent. 2represents a p-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, or a divalent heterocyclic group which may have a substituent. p represents an integer of 1 to 4. When p is an integer of 2 or more, a plurality of A 2 may be the same or different. The -N=N- bond may be replaced with a -C=C-, -COO-, -NHCO-, or -N=CH- bond as long as the compound exhibits absorption in the visible region. (hereinafter, may be referred to as "compound (I)").
[0057] Examples of the monovalent heterocyclic group include groups in which one hydrogen atom has been removed from a heterocyclic compound such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole. Examples of the divalent heterocyclic group include groups in which two hydrogen atoms have been removed from the above heterocyclic compounds.
[0058] A 1 and A 3 Phenyl, naphthyl and monovalent heterocyclic groups in the above formula, and A 2 In the above, examples of the substituents that the p-phenylene group, the naphthalene-1,4-diyl group, and the divalent heterocyclic group may optionally have include an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms and having a polymerizable group, an alkenyl group having 1 to 4 carbon atoms; an alkoxy group having 1 to 20 carbon atoms, such as a methoxy group, an ethoxy group, a butoxy group, etc.; an alkoxy group having 1 to 20 carbon atoms and having a polymerizable group; a fluorinated alkyl group having 1 to 4 carbon atoms, such as a trifluoromethyl group; a cyano group; a nitro group; a halogen atom; and a substituted or unsubstituted amino group such as an amino group, a diethylamino group, a pyrrolidino group, etc. (A substituted amino group means an amino group having one or two alkyl groups having 1 to 6 carbon atoms, an amino group having one or two alkyl groups having 1 to 6 carbon atoms and having a polymerizable group, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2 to 8 carbon atoms. An unsubstituted amino group is -NH 2In this regard, examples of the polymerizable group include an acryloyl group, a methacryloyl group, an acryloyloxy group, and a methacryloyloxy group.
[0059] Among the compounds (I), compounds represented by any one of the following formulas (I-1) to (I-8) are preferred. [ka] [In the formulas (I-1) to (I-8), B 1 ~B 30 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the substituted amino group and the unsubstituted amino group are defined above), a chlorine atom, or a trifluoromethyl group. n1 to n4 each independently represent an integer of 0 to 3. If n1 is 2 or more, multiple B 2 may be the same or different, If n2 is 2 or more, multiple B 6 may be the same or different, If n3 is 2 or more, multiple B 9 may be the same or different, If n4 is 2 or more, multiple B 14 may be the same or different.]
[0060] The content of the dichroic dye in the liquid crystal composition forming the vertical polarizing film and the horizontal polarizing film is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, even more preferably 0.1 to 10 parts by mass, and particularly preferably 0.1 to 7 parts by mass, relative to 100 parts by mass of the solid content of the liquid crystal composition, from the viewpoint of improving the alignment of the dichroic dye. If the content of the dichroic dye is within this range, it is preferable because the liquid crystal alignment of the liquid crystal compound is not easily disturbed.
[0061] In the present invention, the liquid crystal composition used to form the vertical polarizing film and the horizontal polarizing film may contain components other than the dichroic dye and the polymerizable liquid crystal compound. Examples of such components include a polymerization initiator, a leveling agent, a solvent, an antioxidant, a photosensitizer, etc. Each of these components may be used alone or in combination of two or more.
[0062] (Polymerization initiator) The polymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active radicals by the action of light is preferable.
[0063] Examples of the polymerization initiator include benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and sulfonium salts.
[0064] Examples of the benzophenone compound include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.
[0065] Examples of the alkylphenone compound include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethan-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexyl phenyl ketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one.
[0066] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0067] Examples of the triazine compound include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethenyl]-1,3,5-triazine. ]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine.
[0068] The polymerization initiator may be commercially available. Examples of commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250 and 369 (BASF); Seikuol (registered trademark) BZ, Z and BEE (Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100 and UVI-6992 (Nippon Kayaku Co., Ltd.); Adeka Optomer SP-152 and SP-170 (ADEKA Co., Ltd.); TAZ-A and TAZ-PP (DKSH Japan Co., Ltd.); and TAZ-104 (Sanwa Chemical Co., Ltd.).
[0069] From the viewpoint of preventing the alignment of the polymerizable liquid crystal compound from being disturbed, the content of the polymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 8 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0070] (Leveling agent) The leveling agent has a function of adjusting the fluidity of the liquid crystal composition and making the vertical polarizing film and the horizontal alignment film flatter, and can be exemplified by a surfactant. Preferred leveling agents include a leveling agent mainly composed of a polyacrylate compound and a leveling agent mainly composed of a fluorine atom-containing compound.
[0071] Examples of leveling agents containing a polyacrylate compound as a main component include BYK-350, BYK-352, BYK-353, BYK-354, BYK-355, BYK-358N, BYK-361N, BYK-380, BYK-381, and BYK-392 (BYK Chemie).
[0072] Examples of leveling agents containing a fluorine atom-containing compound as a main component include Megafac (registered trademark) R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-471, F-477, F-479, F-482, and F-483 (DIC Corporation); Surflon (registered trademark) S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, and SA-100 (AGC Seimi Chemical Co., Ltd.); E1830 and E5844 (Daikin Industries, Ltd.); F-top EF301, EF303, EF351, and EF352 (Mitsubishi Materials Electronic Chemicals Co., Ltd.).
[0073] The content of the leveling agent is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 5 parts by mass or less, more preferably 3 parts by mass or less, based on 100 parts by mass of the polymerizable liquid crystal compound. If the content of the leveling agent is within the above range, the obtained liquid crystal cured film tends to be smoother, which is preferable. If the content of the leveling agent relative to the polymerizable liquid crystal compound exceeds the above range, the obtained liquid crystal cured film tends to be uneven or the alignment tends to be disturbed, which is not preferable. The vertical polarizing film and the horizontal polarizing film may contain two or more types of leveling agents.
[0074] (solvent) The solvent is preferably one which can completely dissolve the polymerizable liquid crystal compound and is preferably a solvent which is inactive to the polymerization reaction.
[0075] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene, and nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorine-containing solvents such as chloroform and chlorobenzene. These solvents may be used alone or in combination of two or more.
[0076] The content of the solvent is preferably 50 to 98% by mass based on the total amount of the liquid crystal composition, in other words, the ratio of the vertical polarizing film and horizontal polarizing film components is preferably 2 to 50% by mass based on the total amount of the liquid crystal composition. When the solid content is 50% by mass or less with respect to the total amount of the liquid crystal composition, the viscosity of the liquid crystal composition is low, and therefore the thickness of the cured liquid crystal film becomes substantially uniform, and the vertical polarizing film and the horizontal polarizing film tend not to have unevenness. In addition, the solid content can be determined in consideration of the thickness of the vertical polarizing film and the horizontal polarizing film to be manufactured.
[0077] (Antioxidants) By blending an antioxidant, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. The antioxidant may be a primary antioxidant selected from phenol-based antioxidants, amine-based antioxidants, quinone-based antioxidants, and nitroso-based antioxidants, or a secondary antioxidant selected from phosphorus-based antioxidants and sulfur-based antioxidants. In order to polymerize the polymerizable liquid crystal compound without disturbing the alignment of the polymerizable liquid crystal compound, the content of the antioxidant is usually 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. The antioxidants can be used alone or in combination of two or more kinds.
[0078] (Photosensitizer) By using a photosensitizer, the photopolymerization initiator can be made highly sensitive. Examples of the photosensitizer include xanthones such as xanthone and thioxanthone; anthracenes having a substituent such as anthracene and alkyl ether; phenothiazine; and rubrene. The photosensitizer can be used alone or in combination of two or more kinds. The content of the photosensitizer is usually 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0079] (Method of manufacturing vertical and horizontal polarizing films) In the present invention, the vertical polarizing film and the horizontal polarizing film are, for example, A step of obtaining a liquid crystal composition by stirring a polymerizable liquid crystal compound, a dichroic dye, and optionally an additive such as a solvent at a predetermined temperature; forming a coating film of the liquid crystal composition; and A step of drying the coating film to form a dry coating film. The composition can be produced by a method comprising the steps of:
[0080] The temperature when the polymerizable liquid crystal compound and the dichroic dye, and optionally additives such as a solvent, are stirred is usually 0 to 100° C., and preferably 10 to 90° C. The stirring method is not particularly limited, and stirring can be performed by a conventionally known method.
[0081] The coating film of the liquid crystal composition can be formed, for example, by applying the liquid crystal composition onto a substrate and an alignment film. Examples of the substrate include glass substrates and film substrates, but resin film substrates are preferred from the viewpoint of processability. Examples of the resin constituting the film substrate include polyolefins such as polyethylene, polypropylene, and norbornene-based polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid esters; polyacrylic acid esters; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; plastics such as polyphenylene sulfide and polyphenylene oxide. Such resins can be formed into a film by known means such as solvent casting and melt extrusion to form a substrate. The substrate surface may have a protective layer formed from an acrylic resin, a methacrylic resin, an epoxy resin, an oxetane resin, a urethane resin, a melamine resin, or the like, and may be subjected to a surface treatment such as a release treatment such as silicone treatment, a corona treatment, or a plasma treatment.
[0082] Commercially available products may be used as the substrate. Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd., such as Fujitac Film; cellulose ester substrates manufactured by Konica Minolta Opto, Inc., such as "KC8UX2M", "KC8UY", and "KC4UY". Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany), such as "Topas (registered trademark)", cyclic olefin resins manufactured by JSR Corporation, such as "Arton (registered trademark)", cyclic olefin resins manufactured by Zeon Corporation, such as "ZEONOR (registered trademark)" and "ZEONEX (registered trademark)", and cyclic olefin resins manufactured by Mitsui Chemicals, Inc., such as "Apel (registered trademark)". Commercially available cyclic olefin resin substrates may also be used. Examples of commercially available cyclic olefin resin substrates include cyclic olefin resin substrates manufactured by Sekisui Chemical Co., Ltd., such as "S-Cina (registered trademark)" and "SCA40 (registered trademark)"; cyclic olefin resin substrates manufactured by Optes Inc., such as "ZEONORFILM (registered trademark)"; and cyclic olefin resin substrates manufactured by JSR Corporation, such as "ARTONFILM (registered trademark)."
[0083] From the viewpoints of ease of peeling off the substrate, ease of handling the substrate, and the like, the thickness of the substrate is usually from 5 to 300 μm, and preferably from 10 to 150 μm.
[0084] Examples of a method for applying the liquid crystal composition to a substrate or the like include known methods such as application methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator methods, and printing methods such as flexography.
[0085] Next, the solvent is removed by drying or the like to form a dried coating film. Examples of drying methods include natural drying, ventilation drying, heat drying, and reduced pressure drying. In this case, the coating film obtained from the liquid crystal composition is heated to dry and remove the solvent from the coating film, and the liquid crystal compound can be aligned vertically or horizontally to the coating film plane. The heating temperature of the coating film can be appropriately determined in consideration of the liquid crystal compound used and the material of the substrate on which the coating film is formed, but it is necessary that the temperature is equal to or higher than the liquid crystal phase transition temperature in order to phase-transition the liquid crystal compound to a liquid crystal layer state. In order to vertically or horizontally align the liquid crystal compound while removing the solvent contained in the liquid crystal composition, the liquid crystal composition can be heated to a temperature equal to or higher than the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the liquid crystal compound contained in the liquid crystal composition. The liquid crystal phase transition temperature can be measured, for example, using a polarizing microscope equipped with a temperature control stage, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), etc. When two or more liquid crystal compounds are used in combination, the phase transition temperature means a temperature measured in the same manner as when one type of polymerizable liquid crystal compound is used, using a mixture of polymerizable liquid crystal compounds in which all polymerizable liquid crystal compounds constituting the liquid crystal composition are mixed in the same ratio as the composition in the liquid crystal composition. It is generally known that the liquid crystal phase transition temperature of the polymerizable liquid crystal compound in the liquid crystal composition may be lower than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound alone.
[0086] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type and boiling point of the solvent, and the amount thereof, but is usually 15 seconds to 10 minutes, and preferably 0.5 to 5 minutes.
[0087] When a polymerizable liquid crystal compound is used as the liquid crystal compound, the polymerizable liquid crystal compound is polymerized in the obtained dry coating film while maintaining the vertical or horizontal alignment state of the polymerizable liquid crystal compound, thereby forming a vertical polarizing film. The polymerization method includes a thermal polymerization method or a photopolymerization method, but the photopolymerization method is preferable from the viewpoint of easy control of the polymerization reaction. In the photopolymerization, the light to be irradiated to the dry coating film is appropriately selected according to the type of photopolymerization initiator contained in the dry coating film, the type of polymerizable liquid crystal compound (particularly, the type of polymerizable group possessed by the polymerizable liquid crystal compound) and the amount thereof. Specific examples thereof include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays and γ-rays, and active electron beams. Among them, ultraviolet light is preferable from the viewpoint of easy control of the progress of the polymerization reaction and the viewpoint of being able to use a photopolymerization device that is widely used in this field, and it is preferable to select the type of polymerizable liquid crystal compound and photopolymerization initiator contained in the polymerizable liquid crystal composition so that the photopolymerization can be performed by ultraviolet light. In addition, during polymerization, the polymerization temperature can be controlled by irradiating light while cooling the dried coating film with an appropriate cooling means. By employing such a cooling means, polymerization of the polymerizable liquid crystal compound can be carried out at a lower temperature, and even if a substrate having a relatively low heat resistance is used, a vertical or horizontal polarizing film can be appropriately formed. In addition, it is also possible to promote the polymerization reaction by increasing the polymerization temperature within a range in which defects due to heat during light irradiation (such as deformation of the substrate due to heat) do not occur. During photopolymerization, a patterned vertical or horizontal polarizing film can also be obtained by performing masking, development, etc.
[0088] Examples of the light source of the active energy rays include a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave excited mercury lamp, and a metal halide lamp.
[0089] The UV irradiation intensity is usually 10 to 3,000 mW / cm2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a photopolymerization initiator. The time for light irradiation is usually 0.1 seconds to 10 minutes, preferably 0.1 seconds to 5 minutes, more preferably 0.1 seconds to 3 minutes, and further preferably 0.1 seconds to 1 minute. When irradiating once or multiple times with such ultraviolet irradiation intensity, the integrated light amount is 10 to 3,000 mJ / cm. 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 It is.
[0090] The thickness of the vertical polarizing film and the horizontal polarizing film can be appropriately selected depending on the display device to which they are applied, and is preferably 0.1 to 10 μm, more preferably 0.2 to 5 μm, even more preferably 0.2 to 3 μm, still more preferably 0.5 to 5 μm, and particularly preferably 0.5 to 3 μm. When the thickness of the vertical polarizing film and the horizontal polarizing film is within the above range, the laminate can be made thinner. The thickness of the vertical polarizing film and the horizontal polarizing film can be measured using, for example, a laser microscope, a stylus-type film thickness meter, or the like.
[0091] In one embodiment of the present invention, a coating film of the liquid crystal composition is formed on an alignment film. The alignment film has an alignment regulating force that aligns the liquid crystal compound in a desired direction. Among these, an alignment film having an alignment regulating force that aligns the liquid crystal compound in the horizontal direction is sometimes called a horizontal alignment film, and an alignment film having an alignment regulating force that aligns the liquid crystal compound in the vertical direction is sometimes called a vertical alignment film. The alignment regulating force can be arbitrarily adjusted by the type of alignment film, surface state, rubbing conditions, etc., and when the alignment film is formed from a photoalignable polymer, it can be arbitrarily adjusted by the polarized light irradiation conditions, etc.
[0092] The alignment film preferably has solvent resistance so that the liquid crystal composition is not dissolved when applied, and also has heat resistance to remove the solvent and to a heat treatment for aligning the liquid crystal compound, which will be described later.
[0093] Examples of the oriented polymer include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and polyamic acids, which are hydrolyzates thereof, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among them, polyvinyl alcohol is preferred. The oriented polymers can be used alone or in combination of two or more kinds.
[0094] An alignment film containing an alignment polymer is usually obtained by applying a composition in which an alignment polymer is dissolved in a solvent (hereinafter, sometimes referred to as an "alignment polymer composition") to a substrate and removing the solvent, or by applying an alignment polymer composition to a substrate, removing the solvent, and rubbing (rubbing method). Examples of the solvent include the same solvents as those exemplified above as solvents that can be used in the liquid crystal composition.
[0095] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer material can be completely dissolved in the solvent, and is preferably 0.1 to 20% in terms of solid content relative to the solution, and more preferably about 0.1 to 10%.
[0096] As the oriented polymer composition, a commercially available alignment film material may be used as it is. Examples of commercially available alignment film materials include Sunever (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).
[0097] The method for applying the alignment polymer composition to the substrate may be the same as the method exemplified for applying the liquid crystal composition to the substrate.
[0098] Methods for removing the solvent contained in the orientable polymer composition include natural drying, ventilation drying, heat drying, and reduced pressure drying.
[0099] Photo-alignment films for forming vertical and horizontal polarizing films are usually obtained by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film forming composition") to a substrate, removing the solvent, and then irradiating the substrate with ultraviolet light. The ultraviolet light irradiated here is usually unpolarized.
[0100] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it includes groups involved in photoreactions that induce molecular alignment or are the origin of liquid crystal alignment ability, such as isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, caused by irradiation with light. Among them, groups involved in dimerization reaction or photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) is particularly preferred.
[0101] Examples of the photoreactive group having a C=C bond include a vinyl group, a polyene group, a stilbene group, a stilbazolium group, a chalcone group, and a cinnamoyl group. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.
[0102] Among them, photoreactive groups involved in photodimerization are preferred, and cinnamoyl and chalcone groups are preferred because the amount of polarized light irradiation required for photoalignment is relatively small and a photoalignment film having excellent thermal stability and stability over time is easily obtained. As the polymer having a photoreactive group, one having a cinnamoyl group such that the terminal of the polymer side chain has a cinnamic acid structure is particularly preferred.
[0103] A photo-alignment layer can be formed on a substrate by applying the photo-alignment film-forming composition on the substrate. The solvent contained in the composition can be the same as the solvents exemplified above as the solvents usable for the liquid crystal composition, and can be appropriately selected depending on the solubility of the polymer or monomer having a photoreactive group.
[0104] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted depending on the type of polymer or monomer and the thickness of the desired photo-alignment film, but is preferably at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, based on the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film may contain a polymer material such as polyvinyl alcohol or polyimide, or a photosensitizer, within a range that does not significantly impair the properties of the photo-alignment film.
[0105] The method of applying the composition for forming a photo-alignment film to a substrate may be the same as the method of applying the oriented polymer composition to a substrate. Examples of the method of removing the solvent from the applied composition for forming a photo-alignment film include natural drying, ventilation drying, heat drying, and reduced pressure drying.
[0106] The polarized light may be irradiated by directly irradiating the polarized UV light onto the composition for forming a photo-aligned film coated on the substrate after removing the solvent, or by irradiating the polarized light from the substrate side and transmitting the polarized light. In addition, it is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The light from the light source can be irradiated by passing through an appropriate polarizer to irradiate the polarized UV light. As such a polarizer, a polarizing filter, a polarizing prism such as a Glan-Thompson or Glan-Taylor type polarizer, or a wire grid type polarizer can be used.
[0107] If masking is performed during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.
[0108] A groove alignment film is a film that has a concave-convex pattern or multiple grooves on the film surface. When a liquid crystal compound is applied to a film with multiple equally spaced linear grooves, the liquid crystal molecules are oriented in the direction along the grooves.
[0109] Methods for obtaining a groove alignment film include a method in which the surface of a photosensitive polyimide film is exposed to light through an exposure mask having slits in a pattern shape, followed by development and rinsing to form an uneven pattern; a method in which a layer of uncured UV-curable resin is formed on a plate-shaped master having grooves on its surface, the formed resin layer is transferred to a substrate and then cured; and a method in which a roll-shaped master having multiple grooves is pressed against an uncured UV-curable resin film formed on a substrate to form unevenness, followed by curing.
[0110] As a material that exhibits an alignment control force that aligns liquid crystal compounds in the vertical and horizontal directions relative to the coating film plane, in addition to the above-mentioned alignment polymers, fluorine-based polymers such as perfluoroalkyls, silane compounds, and polysiloxane compounds obtained by condensation reactions thereof may be used.
[0111] When a silane compound is used as a material for forming an alignment film, a compound containing Si and C elements as constituent elements is preferable from the viewpoint of easily reducing surface tension and easily increasing adhesion with a layer adjacent to the alignment film, and a silane compound can be suitably used. The alignment control force can be increased by using a silane compound. These silane compounds may be used alone or in combination of two or more, or may be used in combination with other materials.
[0112] The thickness of the alignment film (alignment film containing an alignment polymer or photoalignment film) is usually in the range of 10 to 10,000 nm, preferably in the range of 10 to 1000 nm, more preferably 10 to 500 nm or less, even more preferably 10 to 300 nm, and particularly preferably 50 to 250 nm.
[0113] In another embodiment of the present invention, the coating film of the liquid crystal composition does not require an alignment film and can be formed directly on a substrate. In this embodiment, the liquid crystal composition for forming a vertical polarizing film usually contains an alignment promoter. In the present invention, the alignment promoter means a material that promotes the liquid crystal alignment of the liquid crystal compound in a desired direction. Examples of the alignment promoter that promotes the alignment of the liquid crystal compound include an ionic compound consisting of nonmetallic atoms and a nonionic silane compound. It is preferable that the liquid crystal composition forming the vertical polarizing film contains at least one of an ionic compound consisting of nonmetallic atoms and a nonionic silane compound, and it is more preferable that the liquid crystal composition forming the vertical polarizing film contains both an ionic compound consisting of nonmetallic atoms and a nonionic silane compound.
[0114] <First phase shifter> In the present invention, the first retarder exhibiting in-plane retardation is usually a stretched film (retardation film), and may be a retardation film formed from a composition containing a polymerizable liquid crystal compound (hereinafter, also referred to as a "polymerizable liquid crystal composition"). A stretched film is preferred from the viewpoint of strength because of its large thickness. The first retarder preferably has a positive wavelength dispersion, but may have a reverse wavelength dispersion.
[0115] The film stretched in at least one direction is not particularly limited, but from the viewpoint of dimensional stability and heat resistance stability, a film having a glass transition temperature (Tg) of 80 to 200°C is preferable. For example, polyolefin resins such as polyethylene, polypropylene, polymethylpentene, etc.; fluorinated polyolefin resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyfluorinated ethylene; polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as triacetyl cellulose, diacetyl cellulose, and cellophane; (meth)acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; and other films composed of polystyrene, polycarbonate, polyarylate, polyimide, etc. From the viewpoint of dimensional stability, a film containing a vinyl polymer, a (meth)acrylic resin or a polyolefin resin is preferable, and a film containing a cycloolefin resin is more preferable. The glass transition temperature can be measured, for example, by DSC (differential scanning calorimetry).
[0116] When the first retarder is a stretched film, the film may be, for example, forming the resin, optionally containing additives such as antioxidants and UV absorbers, into a film; and Stretching the film The composition can be produced by a method comprising the steps of:
[0117] Methods for forming a resin into a film include known methods such as melt extrusion, heat press molding, injection molding, and solvent casting.
[0118] Examples of the method of stretching the film include uniaxial stretching and biaxial stretching. Examples of the stretching direction include the machine direction (MD) of the unstretched film, a direction perpendicular to the machine direction (TD), and a direction oblique to the machine direction (MD). The uniaxial stretching may be uniaxial stretching between rolls with different peripheral speeds, or uniaxial stretching using a heated roll. The biaxial stretching may be simultaneous biaxial stretching in which the film is stretched in two stretching directions at the same time, or sequential biaxial stretching in which the film is stretched in a predetermined direction and then stretched in the other direction. The stretching process may be performed, for example, by stretching in the longitudinal direction (machine direction: MD) using two or more pairs of nip rolls with a higher peripheral speed on the outlet side, or by gripping both side ends of the unstretched film with chucks and spreading it in the direction perpendicular to the machine direction (TD). As a method of stretching in an oblique direction, for example, a film roll in which a long film is wound in a roll shape is prepared, the film is continuously unwound from the film roll, and the unwound film is stretched in an oblique direction inclined at a desired angle with respect to the long direction of the film while being transported and heated. The stretching ratio is usually 3 to 8 times. Note that the stretching ratio in biaxial stretching refers to the stretching ratio in the direction in which the stretching ratio is larger.
[0119] The stretched film may be subjected to a surface treatment known in the art, such as a plasma treatment, a corona treatment, an ozone treatment, or an ultraviolet irradiation treatment, before or after the stretching treatment.
[0120] The film stretched in at least one direction as described above can be a commercially available product. Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany) such as "Topas (registered trademark)"; cyclic olefin resins manufactured by JSR Corporation such as "Arton (registered trademark)"; cyclic olefin resins manufactured by Nippon Zeon Corporation such as "ZEONOR (registered trademark)" and "ZEONEX (registered trademark)"; and cyclic olefin resins manufactured by Mitsui Chemicals, Inc. such as "Apel (registered trademark)". Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include cyclic olefin resin substrates manufactured by Sekisui Chemical Co., Ltd. such as "S-Cina (registered trademark)" and "SCA40 (registered trademark)"; cyclic olefin resin substrates manufactured by Optes Co., Ltd. such as "ZEONOR Film (registered trademark)"; and cyclic olefin resin substrates manufactured by JSR Corporation such as "Arton Film (registered trademark)". Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd., such as Fujitac Film; and cellulose ester substrates manufactured by Konica Minolta Opto, Inc., such as "KC8UX2M", "KC8UY", and "KC4UY".
[0121] When the first phase shifter is a retardation film formed from a polymerizable liquid crystal composition, the composition contains a polymerizable liquid crystal compound. The polymerizable liquid crystal compound that can constitute the first phase shifter generally includes a polymer (cured product) obtained by polymerizing the polymerizable liquid crystal compound alone in a state where the polymerizable liquid crystal compound is aligned in a specific direction, and a polymerizable liquid crystal compound that exhibits reverse wavelength dispersion and a polymerizable liquid crystal compound that exhibits positive wavelength dispersion. In the first phase shifter, only one type of polymerizable liquid crystal compound may be used, or both types of polymerizable liquid crystal compounds may be mixed and used. In addition, the polymerizable liquid crystal compound may be used alone or in combination of two or more types. Specific examples of the polymerizable liquid crystal compound that exhibits positive wavelength dispersion include the same compounds as those exemplified in the section on the vertical polarizing film. Examples of the polymerizable liquid crystal compound that exhibits reverse wavelength dispersion include, for example, those described later in the second phase shifter.
[0122] The thickness of the first phase shifter is usually 200 μm or less, preferably 100 μm or less, and more preferably 50 μm or less, from the viewpoint of making the laminate thinner and improving its flexibility. The lower limit of the thickness of the first phase shifter is not particularly limited, but if it is too thin, the strength may decrease, so in the case of a phase difference film, the thickness is usually 5 μm or more, 10 μm to 40 μm, and preferably 15 μm to 35 μm. In the case of a phase difference film, the thickness is usually 1 μm or more, usually 1 μm to 10 μm, and preferably 1 μm to 5 μm.
[0123] <Polarizer> The polarizer may be a stretched film adsorbed with a dye having optical anisotropy, or a polymerizable liquid crystal alignment film. Examples of the stretched film include a film coated with a dye having optical anisotropy. Examples of the dye having optical anisotropy include a dichroic dye.
[0124] A stretched film having an optically anisotropic dye adsorbed thereon is usually produced by sandwiching, via an adhesive, at least one surface of a polarizer produced through a process that involves uniaxially stretching a polyvinyl alcohol-based resin film, dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye, treating the polyvinyl alcohol-based resin film with the dichroic dye adsorbed thereon with an aqueous boric acid solution, and washing the film with water after the treatment with the aqueous boric acid solution, between a transparent protective film.
[0125] Polyvinyl alcohol resins are obtained by saponifying polyvinyl acetate resins. As polyvinyl acetate resins, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith are used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0126] The degree of saponification of the polyvinyl alcohol resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can also be used. The degree of polymerization of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.
[0127] Such a polyvinyl alcohol-based resin is used as a raw film for a polarizing film. The method for forming a film of the polyvinyl alcohol-based resin is not particularly limited, and the film can be formed by a known method. The thickness of the polyvinyl alcohol-based raw film can be, for example, about 10 to 150 μm.
[0128] The uniaxial stretching of the polyvinyl alcohol-based resin film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during the boric acid treatment. It is also possible to perform the uniaxial stretching at these multiple stages. In the uniaxial stretching, the film may be uniaxially stretched between rolls having different peripheral speeds, or may be uniaxially stretched using a heated roll. The uniaxial stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state where the polyvinyl alcohol-based resin film is swollen using a solvent. The stretching ratio is usually about 3 to 8 times.
[0129] Dyeing of a polyvinyl alcohol-based resin film with a dichroic dye is carried out, for example, by a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing the dichroic dye.
[0130] Specifically, iodine and dichroic organic dyes are used as the dichroic pigment. Examples of the dichroic organic dye include dichroic direct dyes made of disazo compounds such as CIDIRECT RED 39, and dichroic direct dyes made of compounds such as trisazo and tetrakisazo. It is preferable that the polyvinyl alcohol resin film is immersed in water before the dyeing process.
[0131] When iodine is used as the dichroic dye, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is usually about 0.01 to 1 part by mass per 100 parts by mass of water. The content of potassium iodide is usually about 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40°C. The immersion time in this aqueous solution (dyeing time) is usually about 20 to 1,800 seconds.
[0132] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing a water-soluble dichroic dye is usually adopted. The content of the dichroic organic dye in this aqueous solution is usually 1×10 -4 ~10 parts by mass, preferably 1 × 10 -3 ~1 part by mass, more preferably 1 × 10 -3 ~1×10 -2 The amount of the dye in the aqueous solution is expressed by parts by mass. This aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The temperature of the aqueous dichroic dye solution used for dyeing is usually about 20 to 80° C. The immersion time in the aqueous solution (dyeing time) is usually about 10 to 1,800 seconds.
[0133] The boric acid treatment after dyeing with a dichroic dye can usually be carried out by immersing the dyed polyvinyl alcohol resin film in an aqueous boric acid solution. The content of boric acid in this aqueous boric acid solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the dichroic dye, this aqueous boric acid solution preferably contains potassium iodide, and in this case, the content of potassium iodide is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the aqueous boric acid solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0134] The polyvinyl alcohol-based resin film after the boric acid treatment is usually washed with water. The washing can be performed, for example, by immersing the boric acid-treated polyvinyl alcohol-based resin film in water. The temperature of the water used in the washing is usually about 5 to 40° C. The immersion time is usually about 1 to 120 seconds.
[0135] After washing with water, a drying treatment is carried out to obtain a polarizer. The drying treatment can be carried out using, for example, a hot air dryer or a far-infrared heater. The temperature for the drying treatment is usually about 30 to 100°C, and preferably 50 to 80°C. The time for the drying treatment is usually about 60 to 600 seconds, and preferably 120 to 600 seconds. The moisture content of the polarizer is reduced to a practical level by the drying treatment. The moisture content is usually about 5 to 20% by weight, and preferably 8 to 15% by weight. When the moisture content is within the above range, a polarizer having appropriate flexibility and excellent thermal stability can be obtained.
[0136] The thickness of the polarizer obtained by the above method is preferably from 5 to 40 μm, and is usually from 20 μm or less, preferably from 15 μm or less, and more preferably from 0.5 to 10 μm.
[0137] Examples of the film coated with a dye having optical anisotropy include a film obtained by coating a composition containing a dichroic dye having liquid crystal properties, or a composition containing a dichroic dye and a polymerizable liquid crystal.
[0138] The film coated with the optically anisotropic dye is preferably thin, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.
[0139] Specific examples of the film coated with a dye having optical anisotropy include the films described in JP-A-2012-33249 and the like.
[0140] <Second phase shifter> The laminate of the present invention includes a second retarder. The second retarder may be used as a single retarder. The second retarder may be incorporated as one of the retarders constituting a multiple retardation plate, in which case the multiple retardation plate includes an additional retarder different from the second retarder. The second retarder is a retarder that exhibits retardation in the in-plane or thickness direction, and specifically may be, for example, a retardation film formed by stretching a thermoplastic resin film or the like and exhibiting retardation in the in-plane or thickness direction; a retardation film composed of a cured film of a composition containing a polymerizable liquid crystal compound and exhibiting retardation in the in-plane or thickness direction, or the like.
[0141] In one embodiment of the present invention, it is preferable that the second phase shifter includes a phase shifter exhibiting an in-plane phase difference. In that case, the second phase shifter is represented by the following formula (9): 120nm≦Re ii (550)≦160nm (9) [In formula (9), Re ii (λ) represents the in-plane retardation value of the second retarder at a wavelength of λ nm. That is, the in-plane retardation Re at a wavelength of 550 nm is satisfied. ii It is preferable that (550) is 120 nm or more and 160 nm or less. Such a retarder functions as a so-called λ / 4 plate.
[0142] In the present invention, the in-plane retardation Re of the second retarder ii When (550) is within the range of the formula (9), when the second retarder is applied to an organic EL display device, the internal reflection light during black display is suppressed. ii (550) is more preferably 130 nm≦Re ii (550)≦150 nm, more preferably 135 nm≦Re ii (550)≦145 nm. The in-plane retardation Re of the second retarder ii The method of adjusting and measuring the (550) is the same as that explained for the in-plane retardation of the first retarder.
[0143] When the second phase element is included alone, the second phase element is represented by the following formula (10): Re ii(450) / Re ii (550)<1.00 (10) [In formula (10), Re ii (λ) has the same meaning as in formula (9) above. It is preferable that the second retarder satisfies the above formula (10). When the second retarder satisfies the above formula (10), the second retarder exhibits so-called reverse wavelength dispersion, in which the in-plane retardation value at a short wavelength is smaller than the in-plane retardation value at a long wavelength. When the laminate of the present invention including the second retarder is applied to an organic EL display device, it can effectively suppress internal reflection of visible light over a relatively wide wavelength range in black display. Even if a small amount of internally reflected light leaks, its coloring is suppressed. The Re of the second retarder ii (450) / Re ii (550) is more preferably 0.90 or less, and further preferably 0.85 or less. ii (450) / Re ii The lower limit of (550) is not particularly limited, and is, for example, 0.7 or more. ii (450) and Re ii (550) can be adjusted in the same manner as Re(450) and Re(550) of the first retarder and can be measured in the same manner.
[0144] In the present invention, the angle between the slow axis of the second phase element and the absorption axis of the polarizer is preferably 25° to 65°, or 125° to 155°. When the angle between the slow axis of the second phase element and the absorption axis of the polarizer satisfies the above range, the second phase element can be a so-called 1 / 4 wavelength plate (λ / 4 plate) that can convert linearly polarized light into circularly polarized light. Therefore, when the second phase element is a λ / 4 plate that satisfies formula (9), the second phase element and the polarizer constitute a so-called circular polarizing plate. The circular polarizing plate outputs unpolarized light incident from the polarizer side as circularly polarized light from the second phase element side. When the angle between the slow axis of the second phase element and the absorption axis of the polarizer satisfies the above range, when a laminate including the second phase element is applied to an organic EL display device, coloring of internally reflected light during black display is further suppressed. The angle between the slow axis of the second phase element and the absorption axis of the polarizer is more preferably 35° to 55°, and ideally 45°. It is more preferable that this angle is in the range of 125° to 145°, and ideally 135°. The angle between the slow axis of the second retarder and the absorption axis of the polarizer can be adjusted and measured in the same manner as the angle between the slow axis of the first retarder and the absorption axis of the polarizer.
[0145] Thermoplastic resin films and polymerizable liquid crystal compounds that can be used for the second phase shifter include the same thermoplastic resin films and polymerizable liquid crystal compounds that can be used for the first phase shifter and the vertical / horizontal polarizing films, and can be prepared in the same manner as the first phase shifter and the vertical / horizontal polarizing films.
[0146] As the polymerizable liquid crystal compound, either a compound showing positive wavelength dispersion or a compound showing reverse wavelength dispersion can be used, and as the compound showing positive wavelength dispersion, for example, the same as those exemplified in the vertical polarizing film section can be used. Also, as the polymerizable liquid crystal compound showing reverse wavelength dispersion, for example, a compound represented by the following formula (X) can be used. [ka]
[0147] In formula (X), Ar represents a divalent group having an aromatic group which may have a substituent. The aromatic group referred to here refers to a ring structure having a π electron number of [4n+2] according to the Huckel rule, and may have two or more Ar groups, such as those exemplified by (Ar-1) to (Ar-23) described later, via a divalent linking group. Here, n represents an integer. When a ring structure is formed by including heteroatoms such as -N= and -S-, the non-covalent bond electron pairs on these heteroatoms also satisfy the Huckel rule and include aromaticity. The aromatic group preferably contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. The aromatic group contained in the divalent group Ar may have one or more aromatic groups. When there is one aromatic group, the divalent group Ar may be a divalent aromatic group which may have a substituent. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other via a divalent bonding group such as a single bond, -CO-O-, or -O-. G 1 and G 2 each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. L 1 , L 2 , B 1 and B. 2 each independently represents a single bond or a divalent linking group. k and l each independently represent an integer of 0 to 3, and satisfy the relationship of 1≦k+l. Here, when 2≦k+l, B 1 and B. 2 , G 1 and G 2 may be the same as or different from each other. E 1 and E 2each independently represents an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms. In addition, a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH 2 - is -O-, -S-, -SiH 2 It may be substituted with -, -C(=O)-. P 1 and P 2 each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0148] G 1 and G 2 are each independently preferably a 1,4-phenylenediyl group optionally substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group optionally substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group. In addition, there are multiple G 1 and G 2 At least one of L is preferably a divalent alicyclic hydrocarbon group. 1 or L 2 G binds to 1 and G 2 It is more preferable that at least one of the groups is a divalent alicyclic hydrocarbon group.
[0149] L 1 and L 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -Ra5 O.C.O.R. a6 -, -R a7 OC=OOR a8 -, -N=N-, -CR c =CR d -, or -C≡C-, where R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms; R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 are each independently preferably a single bond, -OR a2-1 -, -CH 2 -, -CH 2 CH 2 -,-COOR a4-1 -OR- a6-1 -, where R a2-1 , R a4-1 , R a6-1 are each independently a single bond, -CH 2 -, -CH 2 CH 2 - represents either 1 and L 2 are each independently preferably a single bond, -O-, or -CH 2 CH 2 -, -COO-, -COOCH 2 CH 2 -, or -OCO-.
[0150] B 1 and B. 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -, -R a11 COOR a12 -, -R a13 OCOR a14 -, or -R a15 OC=OOR a16 -, where R a9 ~R a16 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1and B. 2 are each independently preferably a single bond, -OR a10-1 -, -CH 2 -, -CH 2 CH 2 -,-COOR a12-1 -OR- a14-1 -, where R a10-1 , R a12-1 , R a14-1 are each independently a single bond, -CH 2 -, -CH 2 CH 2 - represents either 1 and B. 2 are each independently preferably a single bond, -O-, or -CH 2 CH 2 -, -COO-, -COOCH 2 CH 2 -, -OCO-, or -OCOCH 2 CH 2 -It is.
[0151] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≦k+l≦6, preferably k+l=4, and more preferably k=2 and l=2. When k=2 and l=2, a symmetrical structure is obtained, which is preferable.
[0152] P 1 or P 2 Examples of the polymerizable group represented by the formula (I) include an epoxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Of these, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group and an oxetanyl group are preferred, and an acryloyloxy group is more preferred.
[0153] It is preferable that Ar has at least one selected from an aromatic hydrocarbon ring which may have a substituent, an aromatic heterocycle which may have a substituent, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring, and the like, and the benzene ring and the naphthalene ring are preferable. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring. Among them, it is preferable that Ar has a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is more preferable that Ar has a benzothiazole group. In addition, when Ar contains a nitrogen atom, it is preferable that the nitrogen atom has π electrons.
[0154] In formula (X), the total number of π electrons contained in the divalent aromatic group represented by Ar is N π is preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.
[0155] Examples of the aromatic group represented by Ar include the following groups.
[0156] [ka]
[0157] In formulae (Ar-1) to (Ar-23), * represents a linking portion, Z 0 , Z 1 and Z 2each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z 2 may contain a polymerizable group.
[0158] Q 1 and Q 2 are each independently -CR 2‘ R 3‘ -, -S-, -NH-, -NR 2‘ -, -CO- or O-; R 2‘ and R 3‘ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0159] J 1 , and J. 2 each independently represents a carbon atom or a nitrogen atom.
[0160] Y 1 , Y 2 and Y 3 each independently represents an optionally substituted aromatic hydrocarbon group or an optionally substituted aromatic heterocyclic group.
[0161] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6.
[0162] Y 1 , Y 2 and Y 3Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, of which a phenyl group and a naphthyl group are preferred, and a phenyl group is more preferred. Examples of the aromatic heterocyclic group in the formula (I) include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom, such as a nitrogen atom, an oxygen atom, or a sulfur atom, such as a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group, of which a furyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group are preferred.
[0163] Y 1 , Y 2 and Y 3 may each independently be an optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.
[0164] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 is more preferably a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group; Z 1 and Z 2 is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group. 0 , Z 1 and Z 2 may contain a polymerizable group.
[0165] Q 1 and Q 2 -NH-, -S-, -NR 2‘ -, -O- are preferred, R 2‘ is preferably a hydrogen atom, and among these, -S-, -O-, and -NH- are particularly preferable.
[0166] Among the formulae (Ar-1) to (Ar-23), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0167] In formulas (Ar-16) to (Ar-23), Y 1 is the nitrogen atom to which it is bonded and Z 0 and may form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include those mentioned above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. This aromatic heterocyclic group may have a substituent. In addition, Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, etc.
[0168] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition used for forming the first retarder is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 97 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the alignment of the obtained liquid crystal cured film.
[0169] The polymerizable liquid crystal composition used for forming the first retarder may further contain, in addition to the polymerizable liquid crystal compound, additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, a photosensitizer, etc., in amounts that do not affect the effects of the present invention. Examples of these components include the same ones as those exemplified in the section on the vertical polarizing film, and each of them may be used alone or in combination of two or more.
[0170] The retardation film formed from the polymerizable liquid crystal composition is, for example, A step of obtaining a polymerizable liquid crystal composition by stirring a polymerizable liquid crystal compound and, if necessary, an additive such as a solvent at a predetermined temperature; A step of applying the polymerizable liquid crystal composition onto a substrate or an alignment film to obtain a coating film; drying the coating to form a dry coating; and A step of irradiating the dried coating film with active energy rays to form a liquid crystal cured film. The composition can be produced by a method comprising the steps of:
[0171] The coating film of the polymerizable liquid crystal composition can be formed, for example, by applying the polymerizable liquid crystal composition onto a substrate or an alignment film, etc. As the substrate that can be used here, the same substrates as those exemplified as substrates that can be used in the production of a vertical polarizing film can be used.
[0172] The alignment film can be appropriately selected from materials having a regulating force that aligns the polymerizable liquid crystal compound in the horizontal direction relative to the coating film plane. The alignment regulating force can be arbitrarily adjusted by the type of alignment layer, surface state, rubbing conditions, etc., and when it is formed from a photo-alignable polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc. Examples of such materials include those described above as the aligning polymer for forming a coating film of a liquid crystal composition that forms a vertical polarizing film. The alignment film can be obtained by applying a composition containing such a material and a solvent, such as the solvent exemplified in the vertical polarizing film section, to a substrate, removing the solvent, heating the coating film, etc., and further performing a rubbing treatment, a polarized ultraviolet light irradiation treatment, etc. As the alignment film, it is preferable to use a photo-alignment film from the viewpoint of quality.
[0173] Next, the solvent is removed by drying or the like to form a dry coating film. Examples of drying methods include natural drying, ventilation drying, heat drying, and reduced pressure drying. Heat drying is preferred from the viewpoint of productivity, and the heating temperature in this case is preferably high enough to remove the solvent and is equal to or higher than the phase transition temperature of the polymerizable liquid crystal compound. The procedure and conditions in this process are the same as those described in the section on the vertical polarizing film.
[0174] The obtained dried coating film is irradiated with active energy rays (more specifically, ultraviolet rays, etc.) to polymerize the polymerizable liquid crystal compound while maintaining the state in which the polymerizable liquid crystal compound is aligned in the horizontal direction relative to the coating film plane, thereby forming an aligned liquid crystal cured film. The polymerization method is the same as that described in the section on the vertical polarizing film.
[0175] In one embodiment of the present invention, the second phase shifter preferably includes a retardation film which is a cured film of a composition containing a polymerizable liquid crystal compound. When the second phase shifter includes a retardation film, the thickness of the laminate can be suppressed. In addition, when the second phase shifter includes a retardation film, the second phase shifter can have relatively little thermal shrinkage and excellent bending resistance, and is unlikely to crack even when bent. In the present disclosure, the retardation film as the second phase shifter is composed of a single layer made of a cured film of a composition containing a polymerizable liquid crystal compound, or has a two-layer structure consisting of this layer and an alignment layer.
[0176] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition used for forming the second retarder is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the alignment of the obtained liquid crystal cured film.
[0177] The polymerizable liquid crystal composition used for forming the second retarder may further contain additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, a photosensitizer, etc., in addition to the polymerizable liquid crystal compound. Examples of these components include the same ones as those exemplified above as components that can be contained in the vertical polarizing film, and each of them may be used alone or in combination of two or more.
[0178] When the second retarder is a cured product of a composition containing a polymerizable liquid crystal compound, its thickness is usually 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, and usually 0.1 μm or more. When the thickness of the second retarder is within the above range, it is advantageous in terms of thinning. It is easy to make the in-plane retardation and the retardation in the thickness direction to be the desired value, and thus coloring of the internally reflected light during black display is suppressed. When the second retarder is a thermoplastic resin film, its thickness is usually 10 μm to 50 μm, preferably 20 μm to 35 μm.
[0179] In the present invention, when the second phase shifter is incorporated as one of the phase shifters constituting the multiple phase shift plate, examples of the configuration of the multiple phase shift plate include a combination of the above-mentioned second phase shifter exhibiting a phase difference in the plane and an additional phase shifter exhibiting a phase difference in the thickness direction; a combination of the above-mentioned second phase shifter exhibiting a phase difference in the plane and an additional phase shifter exhibiting a phase difference different from that of the second phase shifter in the plane; and the like.
[0180] Such a multi-phase retarder may be, for example, (i) the second retarder exhibiting an in-plane retardation; A so-called positive C layer that shows a phase difference in the thickness direction A multi-phase retarder that can function as a λ / 4 plate for light entering from the front; (ii) the second phase shifter exhibiting an in-plane phase difference, the second phase shifter functioning as a λ / 2 plate and the phase shifter functioning as a λ / 4 plate; A multi-phase retarder that is a combination of the above, which is a so-called broadband retarder that can function as a λ / 4 plate for light coming from the front over a wide wavelength range of visible light; and (iii) the second phase shifter which exhibits an in-plane phase difference and can function as a λ / 4 plate; Unlike other retarders that exhibit phase differences in the thickness direction as well as in the plane. A multi-layer retardation plate that can function as a λ / 4 plate for light coming from the front. etc. The positive C wavelength plate may be prepared from a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound. For example, when a rod-shaped polymerizable liquid crystal compound is used, the positive C wavelength plate is a retardation film obtained when the compound is oriented perpendicular to the in-plane.
[0181] Positive C waveplates that can be used in combination with a second retarder exhibiting an in-plane phase difference can include, for example, those having the optical properties represented by formulas (11) and (13), and may further have the optical properties represented by formula (12). -100nm≦Rth(550)≦-20nm (11) 1.00≦Rth(450) / Rth(550) (12) nx≒ny <nz (13) [In formulas (11) and (12), Rth(λ) represents the thickness retardation of the positive C waveplate at a wavelength of λ nm, and in formula (13), nx represents the refractive index in the in-plane slow axis direction, ny represents the refractive index in the in-plane fast axis direction (direction perpendicular to the slow axis direction), and nz represents the refractive index in the thickness direction.]
[0182] Polymerizable liquid crystal compounds that can be used in a positive C waveplate that can satisfy the above formulas (11) and (13) include rod-shaped polymerizable liquid crystal compounds similar to the polymerizable liquid crystal compounds that can be used in the first retarder and vertical polarizing film.
[0183] The broadband retardation plate may be, for example, a combination of a second retarder (λ / 4 plate) having the optical characteristics expressed by formula (14) and further the optical characteristics expressed by formulas (16) and (17) and a further retarder (λ / 2 plate) having the optical characteristics expressed by formula (15) and further the optical characteristics expressed by formulas (16) and (17). 120nm <Re(550)<160nm (14) 200nm <Re(550)<320nm (15) Re(450) / Re(550)≧1.00 (16) 1.00≧Re(650) / Re(550) (17) [In the formulas (14) to (17), Re(λ) represents the in-plane retardation of each retarder constituting the multiple retardation plate at a wavelength of λ nm]
[0184] The multi-phase retarder can exhibit a retardation in the in-plane or thickness direction based on the retardation of the second retarder and the further retarder. The retardation of the multi-phase retarder can be determined by directly measuring the retardation of the multi-phase retarder.
[0185] The surfaces of the second retarder and the further retarder may be subjected to a surface treatment known in the art, such as a plasma treatment, a corona treatment, an ozone treatment, and an ultraviolet irradiation treatment.
[0186] In the laminate of the present invention, the combination of the polarizer and the second retarder can function as a circular polarizing plate.
[0187] The laminate of the present invention may contain layers other than the first phase shifter, the vertical polarizing film, the polarizer, and the second phase shifter, as long as the effects of the laminate of the present invention are not affected. When the laminate of the present invention contains layers other than the first phase shifter, the vertical polarizing film, the polarizer, and the second phase shifter, the other layers are preferably a pressure-sensitive adhesive layer, a protective layer, etc., and layers known in the art can be used. The other layers preferably have, for example, a total light transmittance of 88% or more and / or a thickness of about 1 to 200 μm so as not to affect the effects (optical properties) that can be achieved by stacking the first phase shifter, the vertical polarizing film, the polarizer and the second phase shifter in this order.
[0188] In the present invention, examples of the adhesive that constitutes the adhesive layer include pressure-sensitive adhesives, drying-hardening adhesives, and chemically reactive adhesives. Examples of the chemically reactive adhesives include active energy ray-curing adhesives. Such adhesives can be any adhesive known in the art.
[0189] The thickness of the pressure-sensitive adhesive layer is not particularly limited since it is determined depending on the type, adhesion, etc., but is usually 0.001 to 40 μm, and preferably 0.01 to 20 μm from the viewpoint of processability and durability.
[0190] The laminate of the present invention may further include a protective layer on, for example, the surface of the first phase shifter opposite to the vertical polarizing film, the surface of the vertical polarizing film opposite to the first phase shifter, the surface of the polarizer on the vertical polarizing film side, the surface of the polarizer on the second phase shifter side, etc. It is preferable that the protective layer to be laminated on the polarizer has an in-plane retardation Re(550) of 0 (zero) nm at a wavelength of 550 nm, or is laminated on one side. By further including a protective layer in the laminate of the present invention, dimensional changes, breakage, cracks, etc. due to heat and / or humidity of the first phase shifter, vertical polarizing film, polarizer, second phase shifter, etc. can be prevented. In addition, deterioration when exposed to ultraviolet rays, etc. can be prevented, and scratches and deterioration of the surfaces of the first phase shifter, vertical polarizing film, polarizer, second phase shifter, etc. during storage and transportation can be prevented.
[0191] Examples of the protective layer include a hard coat layer that can be formed by curing a composition containing a reactive material that forms a crosslinked structure upon exposure to light or thermal energy; a transparent protective film that has transparency that allows light, particularly visible light, to pass through; and the like.
[0192] The hard coat layer can be formed by curing a hard coat composition that simultaneously contains a photocurable (meth)acrylate monomer or oligomer and a photocurable epoxy monomer or oligomer. The photocurable (meth)acrylate monomer can include at least one selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, and polyester (meth)acrylate. The epoxy (meth)acrylate can be obtained by reacting an epoxy compound with a carboxylic acid having a (meth)acryloyl group.
[0193] The hard coat composition may further include one or more selected from the group consisting of a solvent, a photoinitiator, and an additive. The additive may include one or more selected from the group consisting of inorganic nanoparticles, a leveling agent, and a stabilizer, and may further include components commonly used in the art, such as an antioxidant, a UV absorber, a surfactant, a lubricant, and an antifouling agent.
[0194] The transparent protective film preferably has a property of having a transmittance of 88% or more for light having a wavelength of 380 to 780 nm. As the transparent protective film, for example, the same as the above-mentioned examples of the resin substrate usable for the production of the vertical polarizing film can be preferably used.
[0195] The thickness of the hard coat layer and the transparent protective film is preferably 5 μm or less, more preferably 4 μm or less. When the thickness of the hard coat layer and the transparent protective film is the upper limit value or less, the laminate can be thinned while sufficiently protecting the surfaces of the first phase shifter, the vertical polarizing film, the polarizer, the second phase shifter, etc. The thickness of the hard coat layer and the transparent protective film is usually 1 μm or more.
[0196] The protective layer may be laminated via a pressure-sensitive adhesive to the first phase shifter, the vertical polarizing film, the polarizer, the second phase shifter, etc. As the pressure-sensitive adhesive that can be used, the pressure-sensitive adhesives exemplified above can be used in the same manner.
[0197] <Organic EL display device> The laminate of the present invention can be used in various display devices. A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of the display device include a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic electroluminescence (EL) display device, a touch panel display device, an electron emission display device (e.g., a field emission display device (FED) and a surface field emission display device (SED)), electronic paper (electronic ink, a display device using an electrophoretic element, a plasma display device, a projection type display device (e.g., a grating light valve (GLV) display device, a display device having a digital micromirror device (DMD)), and a piezoelectric ceramic display. The liquid crystal display device includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection type liquid crystal display device. These displays may be displays that display two-dimensional images, or stereoscopic displays that display three-dimensional images. In particular, the laminate of the present invention can be suitably used in an organic electroluminescence (EL) display device because the effect of the laminate is easily exhibited remarkably, and the laminate of the present invention can be suitably used in a liquid crystal display device and a touch panel display device. In these displays, spots when viewed obliquely through polarized sunglasses during white display are suppressed. In addition, coloring of internally reflected light during black display can also be suppressed. EXAMPLES
[0198] The present invention will now be described in more detail with reference to the following examples. In the examples, "%" and "parts" mean "% by mass" and "parts by mass", respectively, unless otherwise specified.
[0199] <Example 1> 1. Preparation of the first retarder (HC-COP film 1) with hard coat layer 1 (HC layer 1) A hard-coated cyclic olefin resin film (HC-COP film 1) was prepared by forming an acrylic hard-coat layer 1 (HC layer 1) (thickness 3 μm) on one side of a cycloolefin polymer (COP) film (Zeon Corporation's "ZD12", thickness 22 μm) (COP film 1). The pencil hardness of the surface of the HC layer 1 side of this HC-COP film 1 was 5B. The layer structure of this HC-COP film 1 was HC layer 1 / COP film 1 (ZD12). The in-plane retardation value of this HC-COP film 1 was measured using "KOBRA-WR" manufactured by Oji Scientific Instruments Co., Ltd. The in-plane retardation value Re(450) at a wavelength of 450 nm is 105 nm. The in-plane retardation value Re(550) at a wavelength of 550 nm is 100 nm. The in-plane retardation value Re(650) at a wavelength of 650 nm was 96 nm.
[0200] 2. Preparation of UV-curable adhesive 1 composition The cationic curable components a1 to a3 and the cationic polymerization initiator shown below were mixed in the amounts shown below, and then the cationic polymerization initiator and sensitizer shown below were added in the amounts shown below, further mixed, and the resulting mixture was degassed to prepare ultraviolet curable adhesive composition 1. Note that, among the amounts shown below, the amount of the cationic polymerization initiator (OXT-221) is the amount of the solid content. Cationic curing component a1 (32.5 parts by mass): 3',4'-epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate (Daicel Corporation "CEL2021P") Cationic curing component a2 (7.5 parts by mass): alicyclic structure-containing epoxy compound (Daicel Corporation's "EHPE3150") Cationic curing component a3 (60 parts by mass): 3,3'-(oxybismethylene)bis(3-ethyloxacyclobutane) (manufactured by Toagosei Co., Ltd., "OXT-221") Cationic polymerization initiator (2.25 parts by mass): San-Apro's "CPI-100" (propylene carbonate solution with a solid content of 50% by mass) Sensitizer (2 parts by weight): 1,4-diethoxynaphthalene
[0201] 3. Preparation of composition for forming hard coat layer 2 (HC layer 2) The components shown below were mixed in the amounts shown below and stirred at 80° C. for 1 hour to prepare a composition for forming a hard coat layer 2 (HC layer 2). Acrylate compound (50 parts by mass): dipentaerythritol hexaacrylate Urethane acrylate compound (50 parts by mass): Urethane acrylate (Daicel-Allnex "Ebecryl 4858") Radical polymerization initiator (3 parts by mass): 2-[4-(methylthio)benzoyl]-2-(4-morpholinyl)propane (BASF "Irgacure 907") Solvent (10 parts by weight): Methyl ethyl ketone
[0202] 4. Preparation of release film with HC layer 2 A release-treated surface of a polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical: MRV38 (V04)) (release film) having one side subjected to release treatment was subjected to corona treatment, and the composition for forming the HC layer 2 obtained above was applied by a bar coating method (#2 30 mm / sec) to form a coating film, and a UV irradiation device ("SPOT CURE SP-7" manufactured by Ushio Inc.) was used to apply an exposure dose (accumulated light amount at a wavelength of 365 nm) of 500 mJ / cm to this coating film. 2 By irradiating ultraviolet light so as to obtain a release film with an HC layer, in which an HC layer 2 was formed on the surface of the release film. When measured with a contact film thickness meter, the thickness of this HC layer 2 was 2 μm. The layer structure of this release film with HC layer 2 was HC layer 2 / PET film (MRV38(V04)).
[0203] 5. Preparation of composition for forming vertical polarizing film MC The following polymerizable liquid crystal compounds 1-2, dichroic dyes 1-2, polymerization initiator, leveling agent and solvent were mixed in the amounts shown below and stirred at 80°C for 1 hour to obtain a composition for forming a vertical polarizing film MC. Each dichroic dye is an azo dye described in the examples of JP-A-2013-101328. Polymerizable liquid crystal compounds 1 and 2 were synthesized according to the method described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996).
[0204] ·Polymerizable liquid crystal compound 1 (75 parts by mass): [ka] ·Polymerizable liquid crystal compound 2 (25 parts by mass): [ka] ·Dichroic dye 1 (Magenta dye) (2.8 parts by mass): [ka] Dichroic dye 1 maximum absorption wavelength: 526 nm ·Dichroic dye 2 (Cyan dye) (2.8 parts by mass): [ka] Dichroic dye 2 maximum absorption wavelength: 600 nm Polymerization initiator (6 parts by mass): 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one ("Irgacure 369" manufactured by Ciba Specialty Chemicals) Leveling agent (0.3 parts by mass): Polyacrylate compound (BYK-Chemie "BYK-361N") Solvent (250 parts by weight): o-xylene
[0205] 6. Preparation of composition for forming alignment layer 4 The following alignment polymers were prepared in the amounts shown below, and propylene glycol monomethyl ether was added thereto in the amount shown below to obtain a composition for forming the alignment layer 4. Oriented polymer (0.3 parts by mass): Nissan Chemical Industries, Ltd.'s "Sunever (registered trademark) SE-610" (solution type, solid content concentration 1.0% by mass) Propylene glycol monomethyl ether (27.7 parts by mass)
[0206] 7. Preparation of Vertical Polarizing Film MC 7-1. Preparation of vertical polarizing film MC The composition for forming the alignment layer 4 obtained in the above step 6 was applied onto the HC layer 2 of the release film with the HC layer 2 obtained in the above step 4 (HC layer 2 / PET film (MRV38(V04)) using a bar coater, and dried for 1 minute in a drying oven set at 120°C to form an alignment layer 4. The composition for forming the vertical polarizing film MC obtained in the above step 5 was applied onto the obtained alignment layer 4 using a bar coater, and heated at 100°C for 60 seconds to obtain a dried coating film. This dried coating film was naturally cooled to room temperature, and then, using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.), an integrated light amount at a wavelength of 365 nm was measured under a nitrogen atmosphere at 1000 mJ / cm. 2 A vertical polarizing plate MC consisting of a PET film (MRV38 (V04)) / 2 HC layers / 4 alignment layers / vertical polarizing film MC was obtained by irradiating the dried coating side with ultraviolet light so that the thickness was 2 μm, including the alignment layer, measured with a contact thickness meter.
[0207] 7-2. Measurement of absorbance of vertical polarizing film MC The liquid crystal coated surface of the prepared vertical polarizing plate MC was attached to a 4 x 4 cm x 0.7 mm thick glass plate via a 25 μm pressure-sensitive adhesive (manufactured by Lintec Corporation). After peeling off the PET film, it was set in a UV-visible spectrophotometer (Shimadzu Corporation's "UV-2450") and the absorbance at an elevation angle of 40° was measured. In addition, the maximum absorption wavelength (λ max ), AxC and AxC(z=60) were calculated. Here, the x-axis represents an arbitrary direction within the plane of the vertical polarizing film, the y-axis represents a direction perpendicular to the x-axis within the film plane, and the z-axis represents the thickness direction of the vertical polarizing film. AxC and AxC(z=60) are both absorbances at the maximum absorption wavelength of the vertical polarizing film in the wavelength range of 400 to 750 nm, where AxC represents the absorbance of linearly polarized light oscillating in the x-axis direction, and AxC(z=60) represents the absorbance of linearly polarized light oscillating in the x-axis direction when the film is rotated 60° around the y-axis as the rotation axis. When measuring the absorbance, the sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation, UV-2450) and the absorbance at 800 nm was corrected to zero, and then AxC was measured. For AxC(z=60), the sample was set and tilted in the same manner, and the absorbance at 800 nm was corrected to zero, and then AxC(z=60) was measured. For the vertical polarizing film MC, AxC at 530 nm was 0.115, AxC(z=60) was 0.692, and AxC at 606 nm was 0.062, and AxC(z=60) was 0.639. The maximum absorption wavelength (λ) in the oblique direction was 0.115, AxC(z=60) was 0.692, and AxC at 606 nm was 0.062, AxC(z=60) was 0.639. max ) were 526 and 606 nm.
[0208] 8. Preparation of Polarizing Plate 5 8-1. Preparation of polarizing film A 20 μm thick polyvinyl alcohol resin film (average polymerization degree of about 2400, saponification degree of 99.9 mol% or more) was stretched uniaxially in the longitudinal direction by about 5 times by dry stretching, and then, while maintaining the tension, it was immersed in pure water at a temperature of 60 ° C for 1 minute, and then immersed in an aqueous solution at a temperature of 28 ° C in which the mass ratio of iodine / potassium iodide / water was 0.05 / 5 / 100 for 60 seconds. Then, it was immersed in an aqueous solution at a temperature of 72 ° C in which the mass ratio of potassium iodide / boric acid / water was 8.5 / 8.5 / 100 for 300 seconds. It was then washed with pure water at a temperature of 26 ° C for 20 seconds, and then dried at a temperature of 65 ° C to obtain a polarizing film with a thickness of 8 μm in which iodine was adsorbed and aligned on the polyvinyl alcohol resin film.
[0209] 8-2. Preparation of water-based adhesive A polyvinyl alcohol aqueous solution was prepared by dissolving 3 parts by mass of carboxyl-modified polyvinyl alcohol ("KL-318" manufactured by Kuraray Co., Ltd.) in 100 parts by mass of water. A water-soluble polyamide epoxy resin ("Sumirez Resin 650(30)" manufactured by Taoka Chemical Co., Ltd., solid content concentration 30% by mass) was mixed into the obtained aqueous solution so that the amount of the water was 1.5 parts by mass relative to 100 parts by mass of the water in the aqueous solution, thereby obtaining a water-based adhesive.
[0210] 8-3. Preparation of polarizing plate An HC cyclic olefin resin film (HC-COP film 2) was prepared in which an acrylic hard coat layer 3 (HC layer 3) (thickness 3 μm) was formed on one side of a cycloolefin polymer (COP) film (Zeon Corporation, "ZF") (thickness 13 μm). The pencil hardness of the surface of the HC layer 3 side of this HC-COP film 2 was 5B. The COP film side of this HC-COP film 2 (the side opposite to the HC layer 3 side) was attached to one side of the polarizing film obtained in the above 8-1 via the aqueous adhesive prepared in the above 8-2, to obtain a laminate A (polarizing plate) having a layer structure of HC-COP film 2 / aqueous adhesive / polarizing film. This HC-COP film 2 had an in-plane retardation Re(550) of 0 (zero) nm at a wavelength of 550 nm, and the total light transmittance Ht (%) was measured to be 92.6% using an integrating sphere type light transmittance measuring device ("Haze Meter Hz-5 V3" manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K7105.
[0211] 9. Fabrication of multiple retardation plates 9-1. Preparation of composition for forming alignment layer D An alignment material (weight average molecular weight: 50,000, m:n = 50:50) represented by the following chemical formula was produced according to the method described in JP 2021-196514 A. Two parts by mass of this alignment material was mixed with 98 parts by mass of cyclopentanone (solvent), and the resulting mixture was stirred at 80°C for 1 hour to prepare a composition for forming alignment layer D. Oriented materials: [ka]
[0212] 9-2. Preparation of polymerizable liquid crystal compounds The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) represented by the following chemical formula were prepared. The polymerizable liquid crystal compound (A1) was prepared in the same manner as the method described in JP-A-2019-003177. The polymerizable liquid crystal compound (A2) was prepared in the same manner as the method described in JP-A-2009-173893.
[0213] Polymerizable liquid crystal compound (A1): [ka] Polymerizable liquid crystal compound (B1): [ka]
[0214] A solution was obtained by dissolving 1 mg of the polymerizable liquid crystal compound (A1) in 10 mL of chloroform. The obtained solution was placed in a measurement cell with an optical path length of 1 cm to prepare a measurement sample, and the measurement sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation, "UV-2450") to measure the absorption spectrum. The wavelength at which the maximum absorbance was obtained was read from the obtained absorption spectrum, and the maximum absorption wavelength λ in the wavelength range of 300 to 400 nm was obtained. max was 356 nm.
[0215] 9-3. Preparation of composition for forming retardation film 6 The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 parts by mass of a leveling agent (BM Chemie's "BYK-361N") and 3 parts by mass of a photopolymerization initiator (BASF Japan's "Irgacure OXE-03") were added to 100 parts by mass of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration was 13% by mass. The mixture was stirred at a temperature of 80°C for 1 hour to prepare a composition for forming a retardation film 6.
[0216] 9-4. Preparation of adhesive sheet 1 9-4.(1) Preparation of adhesive composition 1 A mixed solution of 100 parts of ethyl acetate, 99.0 parts of butyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate, and 0.5 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while the internal temperature was raised to 55 ° C. Then, a solution of 0.12 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hour while maintaining the internal temperature at 54 to 56 ° C., and the addition of ethyl acetate was stopped when the concentration of the (meth)acrylic resin became 35% by mass, and the temperature was kept at this temperature until 6 hours had passed since the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass, and acrylic resin solution 2 was prepared. The resulting acrylic resin had a weight average molecular weight Mw of 1.7 million and a molecular weight distribution Mw / Mn of 3.9. Mw and Mn were measured in terms of standard polystyrene using two "TSKgel GMHHR-H(S)" columns manufactured by Tosoh Corporation connected in series as columns in a GPC apparatus, tetrahydrofuran as an eluent, a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40°C, and a flow rate of 1 mL / min.
[0217] To 80 parts by mass of the solid content of the acrylic resin solution 1 obtained above, 20 parts by mass (solid content) of a bifunctional acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.; product number "A-DOG"), 2.5 parts by mass of a crosslinking agent ("Coronate L" manufactured by Tosoh Corporation) (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate (solid content concentration 75% by mass)) based on the active ingredient, 1.5 parts by mass of a photopolymerization initiator ("Irgacure 500" manufactured by Ciba Specialty Chemicals), and 0.3 parts by mass of a silane coupling agent ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) were added, and ethyl acetate was further added so that the solid content concentration became 13%, thereby obtaining a pressure-sensitive adhesive composition 1. The bifunctional acrylate (A-DOG) is a diacrylate of an acetal compound of hydroxypivalaldehyde and trimethylolpropane, and has the following structure: [Chemical formula]
[0218] 9-4.(2) Preparation of the Adhesive Sheet 1 The adhesive composition 1 prepared above was applied to the release-treated surface of a separate film [MRV38 (V04) manufactured by Mitsubishi Chemical Corporation], which is a polyethylene terephthalate film with a release treatment on one side, using an applicator so that the thickness after drying was 15 μm, and then dried at 100 °C for 1 minute to form the adhesive layer 1. Next, the release-treated surface of a separate film [MRF38 manufactured by Mitsubishi Chemical Corporation], which is a polyethylene terephthalate film with a release treatment on one side, was bonded to the surface of the formed adhesive layer 1 opposite to the separator film. Subsequently, ultraviolet rays were irradiated under the following conditions to produce the adhesive sheet 1. The layer structure of this adhesive sheet 1 is Separate Film (MRV38 (V04)) / Adhesive Layer 1 / Separate Film (MRF38). <UV Irradiation Conditions> · Fusion UV Lamp System (manufactured by Fusion UV Systems, using an H bulb) · Integrated light quantity: 250 mJ / cm 2
[0219] 9-5. Preparation of the Horizontally Aligned Retardation Film (Z1) The composition for forming the alignment layer D obtained above was applied to a biaxially stretched polyethylene terephthalate (PET) film (「Diafoil」 manufactured by Mitsubishi Rayon Co., Ltd.) as the base material C using a bar coater to obtain a coated film. After drying the obtained coated film at 120 °C for 2 minutes, it was cooled to room temperature to form a dried film. Then, using a UV irradiation device (「SPOT CURE SP-9」 manufactured by Ushio Electric Inc.), polarized ultraviolet light was irradiated onto this dried film so that the integrated light quantity at a wavelength of 313 nm was 100 mJ / cm 2 to obtain the alignment layer D. When the thickness of this alignment layer D was measured using an ellipsometer (「M-220」 manufactured by Nippon Bunko K.K.), it was 100 nm.
[0220] The composition for forming the retardation film 6 obtained above was applied onto the obtained alignment layer D using a bar coater to form a coating film. This coating film was heated and dried at 120°C for 2 minutes, and then cooled to room temperature to obtain a dry film. Next, a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.) was used to heat the film under a nitrogen atmosphere until the integrated light amount (exposure amount) at 365 nm was 500 mJ / cm. 2 The dried film was irradiated with ultraviolet light so that the horizontally aligned retardation film (horizontally aligned liquid crystal cured film) 6 was formed on the alignment layer D, thereby obtaining a horizontally aligned retardation film (Z1). The horizontally aligned retardation film 6 constituting the horizontally aligned retardation film (Z1) is a retardation film in which the polymerizable liquid crystal compound is cured in a state in which it is aligned horizontally relative to the plane of the substrate C. The layer structure of the horizontally aligned retardation film (Z1) is substrate C / alignment layer D / horizontally aligned retardation film 6. The thickness of the horizontally aligned retardation film 6 measured using a laser microscope (Olympus Corporation, "LEXT OLS4100") was 2.0 μm.
[0221] The surface of the horizontally aligned retardation film 6 of the horizontally aligned retardation film (Z1) obtained above was subjected to corona treatment, and the adhesive layer 1 obtained by peeling off the separate films on both sides from the adhesive sheet 1 was attached to a glass plate, and the substrate C was peeled off and removed to obtain a measurement sample having a configuration of alignment layer D / horizontally aligned retardation film 6 / adhesive layer 1 / glass plate. The in-plane retardation value of this measurement sample was measured using a retardation measurement device (Oji Scientific Instruments Co., Ltd. "KOBRA-WR"). The in-plane retardation values for light with wavelengths of 450 nm, 550 nm, and 650 nm were calculated from the measurement results of the in-plane retardation for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm using Cauchy's dispersion formula. The in-plane retardation Re(450) at a wavelength of 450 nm was 122 nm, the in-plane retardation Re(550) at a wavelength of 550 nm was 140 nm, and the in-plane retardation Re(650) at a wavelength of 650 nm was 144 nm. The relationship between the in-plane retardation at each wavelength was as follows: Re(450) / Re(550)=0.87 Re(650) / Re(550)=1.03 [In the formula, Re(450) represents the in-plane retardation value for light having a wavelength of 450 nm, Re(550) represents the in-plane retardation value for light having a wavelength of 550 nm, and Re(650) represents the in-plane retardation value for light having a wavelength of 650 nm.]
[0222] 9-6. Preparation of composition for forming retardation film 7 A composition for forming retardation film 7 was prepared by mixing 100 parts by mass of a polymerizable liquid crystal compound ("Paliocolor LC242" sold by BASF Japan), 0.1 parts by mass of a leveling agent ("BYK-361N" manufactured by BYK-Chemie), and 2.5 parts by mass of a photopolymerization initiator ("Omnirad907" manufactured by IGM Resin BV), adding 400 parts by mass of propylene glycol 1-monomethyl ether 2-acetate (PGME), and stirring at a temperature of 80°C for 1 hour.
[0223] The polymerizable liquid crystal compound "Paliocolor LC242" is a compound represented by the following chemical formula. [ka]
[0224] 9-7. Preparation of oriented polymer composition 2-Butoxyethanol was added to an oriented polymer (Nissan Chemical Industries, Ltd., "Sunever SE-610") so that the solid content concentration became 1% by mass, thereby obtaining an oriented polymer composition.
[0225] 9-8. Preparation of vertically aligned retardation film (Z2) One side of a cycloolefin polymer (COP) film (ZF manufactured by Zeon Corporation) (COP film ZF) was subjected to a corona treatment using a corona treatment device (AGF-B10 manufactured by Kasuga Electric Co., Ltd.), and then the above-obtained oriented polymer composition was applied to the corona-treated side using a bar coater and dried at 90°C for 1 minute to obtain an orientation layer 8. The thickness of the obtained orientation layer 8 was measured with a laser microscope and found to be 30 nm. The above-obtained composition for forming the retardation film 7 was applied to the obtained orientation layer 8 using a bar coater and dried at 90°C for 1 minute to form a dry film. Using a high-pressure mercury lamp (Uniqure VB-15201BY-A manufactured by Ushio Electric Co., Ltd.), the accumulated light amount (exposure amount) at 365 nm was 1000 mJ / cm under a nitrogen atmosphere. 2 The vertically aligned retardation film (Z2) was obtained by irradiating the dried film with ultraviolet light so that the vertically aligned retardation film (vertically aligned liquid crystal cured film) 7 was formed. The layer structure of this vertically aligned retardation film (Z2) was COP film ZF / alignment layer 8 / vertically aligned retardation film 7. The thickness of the formed vertically aligned retardation film 7 was measured with a laser microscope and found to be 450 nm. The in-plane retardation of this vertically aligned retardation film (Z2) was measured with a retardation measuring device (Oji Scientific Instruments Co., Ltd. "KOBRA-WR"). As a result, the in-plane retardation Re(550) at a wavelength of 550 nm was 1 nm, and the retardation Rth(550) in the thickness direction at a wavelength of 550 nm was -70 nm. This indicates that the film has the optical properties represented by the following formula (3). The COP film ZF used has a phase difference of approximately 0 at a wavelength of 550 nm, and the alignment layer 8 constituting the vertically aligned retardation film (Z2) also has an in-plane phase difference of approximately 0 at a wavelength of 550 nm, so the measured Re(550) and Rth(550) are the optical properties of the vertically aligned retardation film 7 constituting the vertically aligned retardation film (Z2). nx≒ny <nz (3) [nx is the in-plane refractive index in the slow axis direction, ny is the in-plane refractive index in the fast axis direction (the direction perpendicular to the slow axis direction), and nz is the refractive index in the thickness direction.]
[0226] 9-9. Preparation of UV-curable adhesive composition 9 The cationic curable components a1 to a3 and a cationic polymerization initiator shown below were mixed in the amounts shown below, and then the cationic polymerization initiator and sensitizer shown below were further mixed in the amounts shown below. The resulting mixture was degassed to prepare ultraviolet-curable adhesive composition 9. Cationic curing component a1 (70 parts by mass): 3',4'-epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate (Daicel Corporation "CEL2021P") Cationic curing component a2 (20 parts by mass): Neopentyl glycol diglycidyl ether ("EX-211" manufactured by Nagase ChemteX Corporation) Cationic curing component a3 (10 parts by mass): 2-ethylhexyl glycidyl ether ("EX-121" manufactured by Nagase ChemteX Corporation) Cationic polymerization initiator (2.25 parts by mass (solid content)): San-Apro's "CPI-100", a solution of 50% solid content and 50% propylene carbonate) Sensitizer (2 parts by weight): 1,4-diethoxynaphthalene The amount of the cationic polymerization initiator (CPI-100) (2.25 parts by mass) is the amount converted into solid content.
[0227] 9-10. Fabrication of multiple retardation plates The horizontally aligned retardation film 6 side of the horizontally aligned retardation film (Z1) (substrate C / alignment layer D / horizontally aligned retardation film 6) and the vertically aligned retardation film 7 side of the vertically aligned retardation film (Z2) (COP film ZF / alignment layer 8 / vertically aligned retardation film 7) obtained above were each subjected to a corona treatment, and the films were laminated together via an adhesive layer 9 (thickness 2 μm) made of the ultraviolet-curable adhesive composition 9 prepared above. From the vertically aligned retardation film (Z2) side, an ultraviolet irradiation device with a belt conveyor (the lamp used is "H bulb" manufactured by Fusion UV Systems Co., Ltd.) was used to irradiate the films with an irradiation intensity of 390 W / cm in the UVA region (wavelength 320 nm to 390 nm). 2 , the cumulative light intensity is 420mJ / cm 2 Therefore, in the UVB region (wavelength 280 nm to 320 nm), the irradiation intensity is 400 mW / cm 2, the cumulative light intensity is 400mJ / cm 2 The ultraviolet-curable adhesive composition was cured by irradiating ultraviolet light so as to form an adhesive layer 9, thereby obtaining a laminate B. The layer structure of this laminate B was substrate C / alignment layer D / horizontal alignment retardation film 6 / adhesive layer 9 / vertical alignment retardation film 7 / alignment layer 8 / COP film ZF. The in-plane retardation of the laminate B at a wavelength of 550 nm was 140 nm.
[0228] (1) Preparation of optical laminate The substrate C (PET film) of the laminate B [substrate C / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF] obtained in 9-10 above was peeled off to expose the alignment layer D, and the exposed alignment layer D was subjected to a corona treatment. Meanwhile, the separate film (MRF38) of the pressure-sensitive adhesive sheet 1 obtained in 9-4 above was peeled off to expose the pressure-sensitive adhesive layer 1, and the exposed surface of the pressure-sensitive adhesive layer 1 was bonded to the alignment layer D that had been subjected to the corona treatment, to obtain a laminate having a layer structure of separate film (MRV38(V04)) / pressure-sensitive adhesive layer 1 / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF. The other separate film (MRV38(V04)) was peeled off from this laminate to expose the adhesive layer 1, and the polarizing film side of the laminate A (HC-COP film 2 / water-based adhesive / polarizing film) was attached to the exposed adhesive layer 1 to produce a laminate C. The layer structure of this laminate C is HC-COP film 2 / water-based adhesive / polarizing film / adhesive layer 1 / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF.
[0229] (2) Preparation of optical laminate (intermediate body) (preparation of laminate D) The COP film 1 side surface of the HC-COP film 1 obtained in 1. above and the surface of the vertical polarizing film MC obtained in 7. above were each subjected to a corona treatment, and then laminated together via a layer (thickness 2 μm) of the ultraviolet-curable adhesive 1 composition prepared in the above "Preparation of ultraviolet-curable adhesive 1 composition". The vertical polarizing film MC side was exposed to ultraviolet light with a belt conveyor equipped ultraviolet irradiation device (the lamp used was an "H bulb" manufactured by Fusion UV Systems Co., Ltd.) at an irradiation intensity of 390 W / cm in the UVA region (wavelength 320 nm to 390 nm). 2 The total light output is 420 mJ / cm 2 Therefore, in the UVB region (wavelength 280 nm to 320 nm), the irradiation intensity is 400 mW / cm 2 The total light output is 400 mJ / cm 2 The ultraviolet-curable adhesive 1 composition was cured by irradiating ultraviolet light so as to form an adhesive layer, thereby obtaining a laminate D. The layer structure of this laminate D was HC layer 1 / COP film 1 (ZD12) / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / PET film (MRV38 (V04)).
[0230] The PET film (MRV38 (V04)) was peeled off from the laminate D obtained in (2) above to expose the HC layer 2, and the surface of the exposed HC layer 2 was subjected to a corona treatment. The separate film (MRF38) was peeled off from the adhesive sheet 1 obtained above (adhesive layer is 5 μm) to expose the adhesive layer 1, which was then attached to the HC layer 2 subjected to the corona treatment above, and the separate film (MRV38 (V04)) was peeled off to expose the adhesive layer 1, thereby obtaining a laminate E. The layer structure of this laminate E was HC layer 1 / COP film 1 (ZD12) / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / adhesive layer 1. The surface of the HC-COP film 2 side of the laminate C was subjected to a corona treatment, and the laminate was attached to the exposed pressure-sensitive adhesive layer 1 of the laminate E to produce an optical laminate MC1. The layer structure of this optical laminate MC1 is HC layer 1 / COP film 1 / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / adhesive layer 1 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF. The laminate was also laminated so that the angle (θ) between the slow axis of the COP film 1 and the absorption axis of the polarizing film was 45°. In the optical laminate MC1, the COP film 1 corresponds to the first retarder, the vertical polarizing film MC / alignment layer 4 corresponds to the vertical polarizing film, and the alignment layer D / horizontally aligned retardation film 6 corresponds to the second retarder.
[0231] <Example 2> An optical laminate MC2 was produced in the same manner as in Example 1, except that a width-direction uniaxially stretched cycloolefin polymer (COP) film ("ZT" manufactured by Zeon Corporation) (COP film 2) (thickness: 21 μm) was used instead of the HC-COP film 1. The layer structure of the optical laminate MC2 is COP film 2 / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / adhesive layer 3 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF. In the optical laminate MC2, the COP film 2 corresponds to the first retarder, the vertical polarizing film MC / alignment layer 4 corresponds to the vertical polarizing film, and the alignment layer D / horizontally aligned retardation film 6 corresponds to the second retarder. The in-plane retardation value of the width-direction uniaxially stretched COP film used here was measured using KOBRA-WR manufactured by Oji Scientific Instruments Co., Ltd. The results were as follows: The in-plane retardation value at a wavelength of 450 nm is Re(450)=134 nm. The in-plane retardation value at a wavelength of 550 nm is Re(550)=132 nm. The in-plane retardation value at a wavelength of 650 nm is Re(650)=131 nm. It was.
[0232] <Example 3> An optical laminate MC3 was produced in the same manner as in Example 1, except that the HC-COP film 1 was replaced with a retardation film Q produced as follows.
[0233] [Preparation of Oriented Polymer Composition 9] Water was added to commercially available polyvinyl alcohol (polyvinyl alcohol 1000 fully saponified type, manufactured by Wako Pure Chemical Industries, Ltd.), and the mixture was heated at 100° C. for 1 hour to obtain an oriented polymer composition 9.
[0234] [Preparation of composition for forming retardation film Q1] 100 parts by mass of polymerizable liquid crystal compound "Paliocolor LC242" (manufactured by BASF Japan), 0.1 parts by mass of leveling agent "BYK-361N" (manufactured by BYK-Chemie), and 2.5 parts by mass of "Omnirad907" (manufactured by IGM Resin BV) as a photopolymerization initiator were added. Furthermore, 400 parts by mass of propylene glycol 1-monomethyl ether 2-acetate (PGME) was added, and the mixture was stirred at a temperature of 80°C for 1 hour to prepare a composition for forming a retardation film Q1. Polymerizable liquid crystal compound LC242: [ka]
[0235] [Preparation of retardation film Q] The oriented polymer composition 9 was applied to a rectangular cut-out triacetyl cellulose film (TAC) (Konica Minolta, Inc., KC4UY), and after heating and drying, an oriented polymer film (oriented layer 9) with a thickness of 100 nm was formed. The surface of the obtained oriented polymer film was subjected to a rubbing treatment at an angle of 15° from the long side direction of the TAC, and the retardation film Q1-forming composition was applied thereon by a bar coater. The obtained coating film was dried at 100°C for 1 minute, and then cooled to room temperature to obtain a dried film. Next, a high-pressure mercury lamp (Ushio Inc., "Uniqueur VB-15201BY-A") was used to expose the film to 1000 mJ / cm2 under a nitrogen atmosphere. 2The dried film was irradiated with ultraviolet light (365 nm standard) to form a retardation film Q1 in which the polymerizable liquid crystal compound was cured in a state of being aligned horizontally relative to the substrate surface, and a retardation film Q consisting of TAC / alignment layer 9 / retardation film Q1 (horizontally aligned liquid crystal cured film) was obtained. The thickness of the obtained retardation film Q1 was measured with a laser microscope and found to be 1.0 μm. The in-plane retardation value was measured using KOBRA-WR manufactured by Oji Scientific Instruments Co., Ltd. As a result, The in-plane retardation value at a wavelength of 450 nm is Re(450)=127 nm. The in-plane retardation value at a wavelength of 550 nm is Re(550)=115 nm. The in-plane retardation value at a wavelength of 650 nm is Re(650)=111 nm. In addition, since the retardation value of TAC at a wavelength of 550 nm is approximately 0, there is no effect on the optical characteristics. The orientation angle was 15° with respect to the longitudinal direction of the TAC. A laminate DQ was obtained in the same manner as in the preparation of the laminate D, except that the retardation film Q obtained above was used instead of the HC-COP film 1, and the corona treatment was performed on the retardation film Q1 side of the retardation film Q. The layer structure of this laminate DQ is TAC / alignment layer 9 / retardation film Q1 / adhesive layer 1 / vertical alignment film MC / alignment layer 4 / HC layer 2 / PET film (MRC38(V04)).
[0236] The layer structure of the optical laminate MC3 is TAC / alignment layer 9 / retardation film Q1 / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / adhesive layer 1 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF. In the optical laminate MC3, the alignment layer 9 / retardation film Q1 corresponds to the first retarder, the vertical polarizing film MC / alignment layer 4 corresponds to the vertical polarizing film, and the alignment layer D / horizontally aligned retardation film 6 corresponds to the second retarder.
[0237] <Example 4> A laminate DZ1 was obtained in the same manner as in the preparation of the laminate D, except that the horizontally aligned retardation film Z1 was used instead of the HC-COP film 1, and the corona treatment was performed on the horizontally aligned retardation film side of the horizontally aligned retardation film Z1. The layer structure of this laminate DZ1 is: substrate C / alignment layer D / horizontally aligned retardation film 6 (horizontally aligned liquid crystal cured film) / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / PET film (MRV38 (V04)). It is. An optical laminate MC4 was produced in the same manner as in Example 1, except that the laminate DZ1 was used instead of the laminate D. When producing the laminate DZ1, the liquid crystal film of the horizontally aligned retardation film (Z1) and the vertical polarizing film MC were bonded together via an adhesive layer 1.
[0238] The layer structure of the optical laminate MC4 is: substrate C / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 1 / vertically aligned polarizing film MC / alignment layer 4 / HC layer 2 / adhesive layer 1 / HC-COP film 2 / water-based adhesive layer / polarizing film / adhesive layer 1 / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF. In the optical laminate MC4, the alignment layer D / horizontally aligned retardation film 6 corresponds to the first retarder, the vertical polarizing film MC / alignment layer 4 corresponds to the vertical polarizing film, and the alignment layer D / horizontally aligned retardation film 6 corresponds to the second retarder.
[0239] <Example 5> In the preparation of the composition for forming the vertical polarizing film MC in the above 7., except that 2.8 parts by mass of the following dichroic dye 3 (yellow dye) was used instead of the dichroic dyes 1 and 2, the same procedure was followed to obtain a composition for forming the vertical polarizing film Y containing the dichroic dye 3, and the same procedure was followed to prepare the vertical polarizing film MC to obtain the vertical polarizing film Y. The AxC of the vertical polarizing film Y was 0.049, the AxC(z=60) was 0.468, and the absorption maximum wavelength (λ max ) was 402 nm. An optical laminate Y1 was obtained in the same manner as in Example 1, except that the vertical polarizing film Y was used instead of the vertical polarizing film MC. ·Dichroic dye 3 (Yellow dye) (2.8 parts by mass): [ka] Dichroic dye 3 maximum absorption wavelength: 400 nm
[0240] <Example 6> An optical laminate Y2 was obtained in the same manner as in Example 2, except that the vertical polarizing film Y was used instead of the vertical polarizing film MC.
[0241] <Example 7> An optical laminate Y3 was obtained in the same manner as in Example 3, except that the vertical polarizing film Y was used instead of the vertical polarizing film MC.
[0242] <Example 8> An optical laminate Y4 was obtained in the same manner as in Example 4, except that the vertical polarizing film Y was used instead of the vertical polarizing film MC.
[0243] <Example 9> In the preparation of the composition for forming the vertical polarizing film MC in the above 7., except that 2.8 parts by mass of dichroic dye 1 (magenta dye) and 2.8 parts by mass of dichroic dye 3 (yellow dye) used in Example 5 were used instead of dichroic dyes 1 and 2, a composition for forming a vertical polarizing film YM containing dichroic dye 1 and dichroic dye 3 was obtained in the same manner as in the preparation of the composition for forming the vertical polarizing film MC, and a vertical polarizing film YM was obtained in the same manner as in the preparation of the vertical polarizing film MC. The AxC at 390 nm of the vertical polarizing film YM was 0.049 and the AxC(z=60) was 0.468. The AxC at 530 nm was 0.115 and the AxC(z=60) was 0.692. The maximum absorption wavelength (λ max ) were 402 and 526 nm. An optical laminate YM1 was obtained in the same manner as in Example 1, except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0244] <Example 10> An optical laminate YM2 was obtained in the same manner as in Example 2, except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0245] <Example 11> An optical laminate YM3 was obtained in the same manner as in Example 3, except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0246] <Example 12> An optical laminate YM4 was obtained in the same manner as in Example 4, except that the vertical polarizing film YM was used instead of the vertical polarizing film MC.
[0247] <Example 13> In the preparation of the composition for forming the vertical polarizing film MC in the above 7., except that 2.8 parts by mass of dichroic dye 2 (cyan dye) was used instead of dichroic dyes 1 and 2, the same procedure was followed to obtain a composition for forming a vertical polarizing film C containing dichroic dye 2, and the same procedure was followed to prepare the vertical polarizing film MC to obtain a vertical polarizing film C. The AxC of the vertical polarizing film C was 0.062, the AxC(z=60) was 0.639, and the absorption maximum wavelength in the oblique direction (λ max ) was 606 nm. An optical laminate C1 was obtained in the same manner as in Example 1, except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0248] <Example 14> An optical laminate C2 was obtained in the same manner as in Example 2, except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0249] <Example 15> An optical laminate C3 was obtained in the same manner as in Example 3, except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0250] <Example 16> An optical laminate C4 was obtained in the same manner as in Example 4, except that the vertical polarizing film C was used instead of the vertical polarizing film MC.
[0251] <Example 17> 10. Preparation of composition for forming horizontal polarizing film The polymerizable liquid crystal compounds 1-2, dichroic dyes 1-3, polymerization initiator, leveling agent and solvent used in the preparation of the above vertical polarizing film were mixed in the amounts shown below, and stirred at 80°C for 1 hour to obtain a composition for forming a horizontal polarizing film.
[0252] 11. Preparation of horizontal polarizer A horizontal polarizing film was prepared in the same manner as the vertical polarizing film, except that the drying conditions after applying the composition for forming the horizontal polarizing film were set to 120 degrees, and a horizontal polarizing plate consisting of a PET film (MRV38 (V04)) / HC layer 2 / alignment layer 4 / horizontal polarizing film was obtained. The thickness of the horizontal polarizing film was 2 μm as measured by a contact film thickness meter.
[0253] 12. Preparation of optical laminate MC' The horizontal polarizing film surface of the horizontal polarizing plate was subjected to a corona treatment, and then attached to the exposed adhesive layer 1 of the laminate E obtained above to produce a laminate F. The layer structure of this laminate F is HC layer 1 / COP film 1 / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / adhesive layer 1 / horizontal polarizing film / alignment layer 4 / HC layer 2 / PET film (MRV38(V04)). The layers were laminated so that the angle (θ) between the slow axis of the COP film 1 and the absorption axis of the horizontal polarizing film was 45°. The substrate C (PET film) of the laminate B obtained in 9-10. above was peeled off to expose the alignment layer D, and the exposed alignment layer D was subjected to a corona treatment. On the other hand, the separate film (MRF38) of the adhesive sheet 1 obtained in 9-4. above was peeled off to expose the adhesive layer 1, and the exposed surface of the exposed adhesive layer 1 was bonded to the alignment layer D that had been subjected to the corona treatment, to obtain a laminate having a layer structure of separate film (MRV38 (V04)) / adhesive layer 1 / alignment layer D / horizontal alignment retardation film 6 / adhesive layer 9 / vertical alignment retardation film 7 / alignment layer 8 / COP film ZF. From this laminate, the other separate film (MRV38 (V04)) was peeled off to expose the adhesive layer 1, and the outermost HC layer 2 that had been peeled off the PET film from the laminate F and subjected to a corona treatment was bonded to the exposed adhesive layer 1 to produce an optical laminate MC'1. The layer structure of this optical laminate MC'1 is HC layer 1 / COP film 1 / adhesive layer 1 / vertical polarizing film MC / alignment layer 4 / HC layer 2 / adhesive layer 1 / horizontal polarizing film / alignment layer 4 / HC layer 2 / adhesive layer 1 / alignment layer D / horizontal alignment retardation film 6 / adhesive layer 9 / vertical alignment retardation film 7 / alignment layer 8 / COP film ZF. The layers were laminated so that the angle (θ) between the slow axis of COP film 1 and the absorption axis of the horizontal polarizing film was 45°. In the optical laminate MC'1, the COP film 1 corresponds to the first retarder, the vertical polarizing film MC / alignment layer 4 corresponds to the vertical polarizing film, and the alignment layer D / horizontally aligned retardation film 6 corresponds to the second retarder.
[0254] <Examples 18 to 32> Other than the laminate A, the same materials as in Examples 2 to 16 were used, and the preparation method was the same as in Example 17 to obtain Examples 18 to 32 including a horizontal polarizing film.
[0255] <Comparative Example 1> The coated surface of the vertical polarizing film MC in Example 1 was subjected to a corona treatment, and then the surface of the adhesive sheet 1 from which the separate film (MRF38) had been peeled off was attached to produce a laminate G. The laminate G was a PET film (MRV38 (V04)) / HC layer 2 / alignment layer 4 / vertical polarizing film MC / adhesive layer 1 / separate film (MRV38 (V04)). The HC-COP film 2 in the laminate C was replaced with the HC-COP film 1, and the HC surface was subjected to a corona treatment, after which the separate film of the laminate G was peeled off to expose the adhesive layer 1, and the laminate was attached to the HC surface of the laminate C via the exposed adhesive layer 1, and the outermost PET film (MRV38 (V04)) was peeled off to obtain Comparative Example 1. The layer structure of this Comparative Example 1 is HC layer 2 / alignment layer 4 / vertical polarizing film MC / adhesive layer 1 / HC-COP film 1 (HC layer / COP film 1) / water-based adhesive / polarizing film / adhesive layer 1 / alignment layer D / horizontally aligned retardation film 6 / adhesive layer 9 / vertically aligned retardation film 7 / alignment layer 8 / COP film ZF. In the laminate of Comparative Example 1, the alignment layer 4 / vertical polarizing film MC corresponds to the vertical polarizing film, the COP film 1 constituting the HC-COP film 1 corresponds to the first retarder, and the alignment layer D / horizontally aligned retardation film 6 corresponds to the second retarder. The HC layer constituting the HC-COP film 1 is non-oriented.
[0256] The characteristics of the retarder, vertical polarizing film, and polarizer used in each of the examples and comparative examples are shown in Tables 1-1 and 1-2. In Tables 1-1 and 1-2, M of the dichroic dye represents a magenta dye, C represents a cyan dye, and Y represents a yellow dye, and θ of the polarizer represents the angle between the slow axis of the first retarder and the absorption axis of the polarizer.
[0257] [Table 1-1] TIFF2025058922000022.tif35170
[0258] [Table 1-2]
[0259] <Evaluation method> 1. Spots when displaying white The front glass and polarizing plate were removed from a Samsung Galaxy S5 (organic electroluminescence display device) to take out the display device. The COP film ZF of the optical laminate produced by the above method was peeled off and attached to the display device taken out above via the adhesive sheet 1. After that, characters were displayed on the screen of the display device, and the presence or absence of spots was visually observed through polarized sunglasses from a direction at an elevation angle of 45° relative to the front of the screen. The screen display at this time was displayed in black against a white background. The display device was rotated in-plane to observe in all directions. A: No visible spots (0% of the white display area of the background) B: Spots are barely visible (more than 0% and less than 10% of the white display area of the background) C: Spots are slightly visible, but no practical problems (more than 10% and less than 50% of the white display area in the background) D: Spots are visible and are problematic for practical use (more than 50% of the white display area in the background) The evaluation results are shown in Table 2.
[0260] 2. Coloring when displaying black The front glass and polarizing plate were removed from the Samsung Galaxy S5 to take out the display device. The COP film ZF of the optical laminate produced by the above method was peeled off and attached to the display device taken out above via the adhesive sheet 1. After that, the reflected hue was confirmed when the display device was viewed with the naked eye from an oblique direction with the power turned off (black display), and was evaluated according to the evaluation criteria shown below. A: I don't feel any color B: Almost no color. C: A slight tint D: The color is clearly visible The evaluation results are shown in Table 2. The reflected hue evaluated above is the hue of the internally reflected light that is reflected inside the organic EL display device and is slightly visible. This internally reflected light is visible when the display is in black. Furthermore, the reflected hue was also confirmed when the display device was viewed with the naked eye from the front with the power turned off, but no color was perceived in any of the examples and comparative examples.
[0261] [Table 2-1]
[0262] [Table 2-2] [Explanation of symbols]
[0263] 1 :First phase shifter 2: Vertical polarizing film 3: Polarizer 4:Second phase shifter 5: Further phase shifters 11:Multiple retardation plate 21: Laminate
Claims
1. A laminate including a first phase shifter, a vertical polarizing film, a polarizer, and a second phase shifter in this order, the first retarder is a retarder exhibiting an in-plane retardation, an angle between a slow axis of the first retarder and an absorption axis of the polarizer is 35° or more and 55° or less, or 125° or more and 145° or less, The vertical polarizing film is a cured product of a composition containing a polymerizable liquid crystal compound and a dichroic dye, and is represented by the following formulas (1) and (2): 0.001≦A×C≦0.3 (1) AxC (z=60) / AxC>2 (2) [In the formulas (1) and (2), AxC and AxC (z=60) are absorbances at the absorption maximum wavelength of the vertical polarizing film in the wavelength range of 400 to 750 nm, AxC represents the absorbance of linearly polarized light vibrating in the x-axis direction, and AxC(z=60) represents the absorbance of linearly polarized light vibrating in the x-axis direction when the vertical polarizing film is rotated 60° around the y-axis as the rotation axis, Here, the x-axis refers to an arbitrary direction in the plane of the vertical polarizing film, the y-axis refers to a direction perpendicular to the x-axis in the film plane, and the z-axis refers to the thickness direction of the vertical polarizing film. Meet the laminate.
2. The vertical polarizing film has an absorption maximum wavelength in an oblique direction of 500 nm or more and less than 700 nm, and the first phase shifter has a formula (3) below: Re(450)≦135nm (3) [In formula (3), Re(450) represents the in-plane retardation value of the first retarder at a wavelength of 450 nm] The laminate according to claim 1 ,
3. The vertical polarizing film has an absorption maximum wavelength in an oblique direction of 400 nm or more and less than 500 nm, and the first phase shifter has the following formulas (4) and (5): Re(550)≧95nm (4) Re(650)≧95nm (5) [In formulas (4) and (5), Re(λ) represents the in-plane retardation value of the first retarder at a wavelength of λ nm] The laminate according to claim 1 , which satisfies at least one of the above.
4. The vertical polarizing film has an absorption maximum wavelength in an oblique direction of 400 nm or more and less than 600 nm, and the first phase shifter has a formula (6) below: Re(650)≧95nm (6) [In formula (6), Re(650) represents the in-plane retardation value of the first retarder at a wavelength of 650 nm] The laminate according to claim 1 ,
5. The vertical polarizing film has a maximum absorption wavelength in an oblique direction of 600 to 700 nm, and the first phase shifter has the following formulas (7) and (8): Re(450)≦135nm (7) Re(550)≦150nm (8) [In formulas (7) and (8), Re(λ) represents the in-plane retardation value of the first retarder at a wavelength of λ nm] The laminate according to claim 1 , which satisfies at least one of the above.
6. The laminate according to claim 1 or 2, wherein the second retarder comprises a cured film of a composition containing a polymerizable liquid crystal compound.
7. The laminate according to claim 1 , wherein the polarizer comprises a cured film of a composition comprising a polymerizable liquid crystal compound and a dichroic dye.
8. An organic electroluminescence display device comprising the laminate according to claim 1 .
Citation Information
Patent Citations
Laminate and display
JP2022176121A